Polishing compositions, semiconductor wetting agents, water-soluble polymers, and methods for producing the same.

JP7933851B2Active Publication Date: 2026-10-13FUJIMI INCORPORATED
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024229660
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2026-10-13
Estimated Expiration
2040-09-08

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、基板の良好な表面状態を達成できる研磨用組成物、半導体用濡れ剤、水溶性高分子が提供される。より詳細には、本発明に係る研磨用組成物および/または半導体用濡れ剤によって研磨および/またはリンスすることで、基板上で観察される欠陥の個数をより減少させることができる。特に、LPD-N(Light Point Defect Non-cleanable)やLPD(Light Point Defect)といった欠陥の減少に効果的である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933851000006
    Figure 0007933851000006
  • Figure 0007933851000007
    Figure 0007933851000007
  • Figure 0007933851000008
    Figure 0007933851000008
Patent Text Reader

Abstract

To provide a polishing composition containing a water-soluble polymer, capable of achieving an excellent surface state on a substrate.SOLUTION: There is provided a polishing composition containing a water-soluble polymer. In the polishing composition, the water-soluble polymer is a water-soluble polymer processed by a method including steps of: preparing a solution by dissolving a raw-material water-soluble polymer into a solvent; and applying a pressure onto the solution by allowing collision in the solution.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to polishing compositions, semiconductor wetting agents, water-soluble polymers, and methods for producing the same. [Background technology]

[0002] Water-soluble polymers are used in a variety of applications, including dispersants, thickeners, emulsion polymerization stabilizers, protective colloids, paints, cosmetics, water-retaining agents, pharmaceutical formulations, and polishing aids. Among these, hydroxyethylcellulose, a semi-synthetic polymer compound, is particularly excellent in properties such as dispersibility and thickening. Hydroxyethylcellulose is used in addition to abrasive grains and water as a polishing aid to protect the substrate surface and improve wettability in the rinsing and polishing processes of various substrates, such as semiconductor substrates represented by silicon wafers.

[0003] Patent Document 1 discloses a method for producing dried hydrophobized hydroxyethyl cellulose, which is useful as an abrasive aid that can improve the polishing speed when combined with abrasive grains. Specifically, Patent Document 1 discloses obtaining dried hydrophobized hydroxyethyl cellulose by drying synthesized undried hydrophobized hydroxyethyl cellulose and then pulverizing it. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2019-104781 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] However, with technological advancements, the surface condition required for polished materials such as semiconductor substrates, semiconductor devices, or silicon wafers is increasingly demanding higher quality.

[0006] Therefore, the present invention aims to provide a polishing composition, a semiconductor wetting agent, a water-soluble polymer, and methods for producing the same, which can achieve a good surface condition of a substrate. [Means for solving the problem]

[0007] The above problems of the present invention can be solved by the following means: A polishing composition comprising abrasive particles and a water-soluble polymer, The water-soluble polymer is The process involves dissolving the raw material water-soluble polymer in a solvent to create a solution, An abrasive composition, which is a water-soluble polymer treated by a method comprising the step of colliding the aforementioned solutions with each other and applying pressure to the solutions.

[0008] A method for producing an abrasive composition comprising abrasive particles and a water-soluble polymer, The process involves dissolving the raw material water-soluble polymer in a solvent to create a solution, A step of causing the solutions to collide with each other and applying pressure to the solutions, A step of mixing abrasive particles into the aforementioned solution under pressure, A method for producing an abrasive composition containing [the specified ingredient].

[0009] Furthermore, the above-mentioned problems of the present invention can also be solved by the following means: A semiconductor wetting agent containing a water-soluble polymer, The water-soluble polymer is The process involves dissolving the raw material water-soluble polymer in a solvent to create a solution, A step of causing the solutions to collide with each other and applying pressure to the solutions, A semiconductor wetting agent, which is a water-soluble polymer treated by a method including [a specific method].

[0010] A method for producing a semiconductor wetting agent containing a water-soluble polymer, The process involves dissolving the raw material water-soluble polymer in a solvent to create a solution, A step of causing the solutions to collide with each other and applying pressure to the solutions, A method for manufacturing a semiconductor wetting agent, including the above.

[0011] Furthermore, the above-described object of the present invention can also be solved by the following means: a step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution, and a step of causing the solutions to collide with each other to apply pressure to the solutions, A water-soluble polymer for use in polishing compositions and / or semiconductor wetting agents, which is treated by a method comprising the steps of.

[0012] a step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution, and a step of causing the solutions to collide with each other to apply pressure to the solutions, A method for producing a water-soluble polymer for use in polishing compositions and / or semiconductor wetting agents, comprising the steps of.

Effects of the Invention

[0013] According to the present invention, a polishing composition, a semiconductor wetting agent, and a water-soluble polymer that can achieve a favorable surface state of a substrate are provided. More specifically, by performing polishing and / or rinsing with the polishing composition and / or semiconductor wetting agent according to the present invention, the number of defects observed on the substrate can be further reduced. It is particularly effective in reducing defects such as LPD-N (Light Point Defect Non-cleanable) and LPD (Light Point Defect).

[0014] Further, according to the present invention, high-molecular-weight components of the water-soluble polymer used for producing the polishing composition and / or the semiconductor wetting agent can be selectively removed. And by the selective removal of these high-molecular-weight components, the filterability of a solution containing the water-soluble polymer, the polishing composition and / or the semiconductor wetting agent can be improved. Furthermore, the high-molecular-weight components can be selectively removed without increasing the amount of impurities contained in the water-soluble polymer and the solution containing the same.

Brief Description of the Drawings

[0015] [Figure 1]Figure 1 shows the GPC elution curves of the raw water-soluble polymer and the treated water-soluble polymer when HEC1 is used as the raw water-soluble polymer in the example. [Figure 2] Figure 2 shows the GPC elution curves of the raw water-soluble polymer and the treated water-soluble polymer when HEC2 was used as the raw water-soluble polymer in the example. [Figure 3] Figure 3 shows the differential molecular weight distribution curves of the raw water-soluble polymer and the treated water-soluble polymer when HEC1 is used as the raw water-soluble polymer in the example. [Figure 4] Figure 4 shows the differential molecular weight distribution curves of the raw water-soluble polymer and the treated water-soluble polymer when HEC2 is used as the raw water-soluble polymer in the example. [Modes for carrying out the invention]

[0016] Embodiments of the present invention will be described below. However, the present invention is not limited to the embodiments described below. In this specification, "X~Y" indicating a range means "X or more and Y or less". Unless otherwise specified, operations and measurements of physical properties, etc., are performed under conditions of room temperature (20°C to 25°C) and relative humidity of 40%RH to 50%RH.

[0017] Although the mechanism by which the above problems can be solved by the present invention is not yet fully clear, the inventors speculate on a part of it as follows.

[0018] In this invention, by applying pressure to a solution containing a raw water-soluble polymer, the entanglement of high molecular weight molecules of the raw water-soluble polymer is resolved, and the molecular chains of the high molecular weight molecules of the raw water-soluble polymer are broken. As a result, the high molecular weight molecules of the raw water-soluble polymer are removed, the viscosity is reduced compared to the raw water-soluble polymer before treatment, and the filterability of the solution, polishing composition, and / or semiconductor wetting agent containing the resulting water-soluble polymer (hereinafter also simply referred to as "treated water-soluble polymer") is improved.

[0019] Furthermore, as a method for applying pressure to a solution containing the raw material water-soluble polymer, the solutions containing the raw material water-soluble polymer collide with each other to apply pressure to the solution, and collisions with other components are not employed, thus making it less likely for impurities to be introduced.

[0020] As a result, high molecular weight substances that cause surface defects can be removed from the raw water-soluble polymer, and the increase in impurities due to the processing of the raw water-soluble polymer can also be prevented. Therefore, it is believed that when polishing and / or rinsing with the polishing composition and / or semiconductor wetting agent according to the present invention, the number of surface defects (e.g., LPD-N and LPD) on the substrate can be further reduced.

[0021] Here, although the mechanism by which high molecular weight molecules are selectively removed is not yet fully understood, the inventors of this invention speculate on a part of it as follows.

[0022] In other words, during the collision process, high molecular weight molecules in the raw material water-soluble polymer have a higher collision frequency than low molecular weight molecules, and high molecular weight molecules contain a proportionally larger number of points where the molecular chain breaks compared to low molecular weight molecules. Therefore, it is thought that high molecular weight molecules are selectively removed.

[0023] It should be noted that the above mechanism is based on speculation, and its accuracy does not affect the technical scope of the present invention.

[0024] The present invention will be described in detail below, but the present invention is not limited to the following description.

[0025] <Polishing compositions and semiconductor wetting agents, as well as methods for manufacturing the same> One embodiment of the present invention relates to an abrasive composition comprising abrasive grains and a water-soluble polymer, wherein the water-soluble polymer is a water-soluble polymer processed by a method comprising the steps of: dissolving a raw material water-soluble polymer in a solvent to make a solution (hereinafter also referred to as the "dissolution step") and making the solutions collide with each other and applying pressure to the solution (hereinafter also referred to as the "collision step").

[0026] Another embodiment of the present invention relates to a semiconductor wetting agent comprising a water-soluble polymer, wherein the water-soluble polymer is a water-soluble polymer treated by a method comprising a dissolution step and a collision step.

[0027] The following describes the treatments applied to the water-soluble polymers used in the polishing composition and / or semiconductor wetting agent of this application.

[0028] <<Processing of water-soluble polymers and processed water-soluble polymers>> One embodiment of the present invention relates to a method for treating a water-soluble polymer used in polishing compositions and / or semiconductor wetting agents, comprising the steps of: dissolving a raw water-soluble polymer in a solvent to make a solution (dissolution step); and colliding the solutions with each other and applying pressure to the solutions (collision step), wherein the method for treating a water-soluble polymer (i.e., a water-soluble polymer to be treated) comprises these steps. Another embodiment of the present invention relates to a water-soluble polymer for use in polishing compositions and / or semiconductor wetting agents, treated by a method comprising the dissolution step and the collision step.

[0029] [Dissolution process] The water-soluble polymer of the present invention is a water-soluble polymer treated by a method that includes a step of dissolving a raw water-soluble polymer in a solvent to prepare a solution (dissolution step).

[0030] In this specification, "dissolve" means to dissolve or disperse. "Dissolve" preferably means that at least a portion is dissolved, and while the remaining portion may be dispersed in the solvent, complete dissolution is particularly preferred.

[0031] (Raw material water-soluble polymer) The type of water-soluble polymer used as a raw material in the present invention is not particularly limited as long as it is a water-soluble polymer compound. Examples of polymer compounds include those containing hydroxyl groups, carboxyl groups, acyloxy groups, sulfo groups, amide structures, imide structures, quaternary ammonium structures, heterocyclic structures, vinyl structures, ether bonds, etc., in their molecules.

[0032] In this specification, "water-soluble" means a solubility of 1 g / 100 mL or more in water (25°C), and "high molecular weight compound" means a compound with a weight-average molecular weight (Mw) of 2,000 or more. The weight-average molecular weight (Mw) can be measured by gel permeation chromatography (GPC), and details of the measurement method are described in the examples.

[0033] As the raw material water-soluble polymer, any of natural polymer compounds, semi-synthetic polymer compounds, or synthetic polymer compounds may be used. Natural polymer compounds are not particularly limited, but polysaccharides are preferred. Semi-synthetic polymer compounds are not particularly limited, but cellulose derivatives and starch derivatives are preferred. Synthetic polymer compounds are not particularly limited, but polymers having oxyalkylene units, polymers having structural units derived from vinyl alcohol, and polymers having nitrogen atoms are preferred. In one embodiment of the present invention, the raw material water-soluble polymer contains a hydroxyl group or an ether group from the viewpoint of improving surface quality. In particular, it is preferable to contain at least one of a polymer having structural units derived from vinyl alcohol and a cellulose derivative. Polishing compositions and / or semiconductor wetting agents containing these polymers easily improve surface quality after polishing and / or rinsing processes. Specific examples of these compounds are given below.

[0034] There are no particular restrictions on the type of polysaccharide used, but examples include carrageenan and xanthan gum.

[0035] Cellulose derivatives are not particularly limited, but examples include hydroxyethylcellulose (hereinafter also simply referred to as "HEC"), hydroxypropylcellulose, hydroxyethylmethylcellulose, hydroxypropylmethylcellulose, methylcellulose, ethylcellulose, ethylhydroxyethylcellulose, carboxymethylcellulose, and other cellulose derivatives, as well as pullulan. One type of cellulose derivative may be used alone, or two or more types may be used in combination. Here, a cellulose derivative refers to a cellulose in which some of the hydroxyl groups of cellulose are replaced with other substituents.

[0036] The starch derivatives are not particularly limited, but examples include cationic starch, phosphate starch, and carboxymethyl starch salts.

[0037] The polymer having oxyalkylene units is not particularly limited, but examples include polyethylene oxide (PEO), polypropylene oxide (PPO), block copolymers of ethylene oxide (EO) and propylene oxide (PO) or butylene oxide (BO), and random copolymers of EO and PO or BO. Among these, block copolymers of EO and PO or random copolymers of EO and PO are preferred. The block copolymer of EO and PO may be a diblock or triblock containing a PEO block and a polypropylene oxide (PPO) block. Examples of the above triblock include PEO-PPO-PEO type triblocks and PPO-PEO-PPO type triblocks. Among these, the PEO-PPO-PEO type triblock is more preferred.

[0038] In a block copolymer or random copolymer of EO and PO, the molar ratio [EO / PO] of EO and PO constituting the copolymer is preferably greater than 1, more preferably 2 or more, and even more preferably 3 or more, from the viewpoint of solubility in water and washability. In a further preferred embodiment, the above molar ratio [EO / PO] is, for example, 5 or more.

[0039] A polymer having structural units derived from vinyl alcohol may contain only vinyl alcohol units (hereinafter also referred to as "VA units") as repeating units, or it may contain repeating units other than VA units (hereinafter also referred to as "non-VA units") in addition to VA units. One type of polymer having structural units derived from vinyl alcohol may be used alone, or two or more types may be used in combination. A vinyl alcohol unit is a structural part represented by the following chemical formula: -CH2-CH(OH)-;. A polymer having structural units derived from vinyl alcohol may be a random copolymer containing VA units and non-VA units, or it may be a block copolymer or a graft copolymer. A polymer having structural units derived from vinyl alcohol may contain only one type of non-VA unit, or it may contain two or more types of non-VA units.

[0040] The polymer having structural units derived from vinyl alcohol used in the raw material water-soluble polymer disclosed herein may be unmodified polyvinyl alcohol (unmodified PVA) or modified polyvinyl alcohol (modified PVA). Here, unmodified PVA refers to a polymer having structural units derived from vinyl alcohol that are produced by hydrolysis (saponification) of polyvinyl acetate and substantially do not contain repeating units other than the vinyl polymerized vinyl acetate structure (-CH2-CH(OCOCH3)-) and VA units. The degree of saponification of the above unmodified PVA may be, for example, 60% or more, and may be 70% or more, 80% or more, or 90% or more from the viewpoint of water solubility. In some embodiments, unmodified PVA with a degree of saponification of 95% or more, or unmodified PVA with a degree of saponification of 98% or more, can be preferably used as the raw material water-soluble polymer.

[0041] Non-VA units that may be included in modified PVA include, but are not limited to, repeating units derived from N-vinyl type monomers or N-(meth)acryloyl type monomers, repeating units derived from ethylene, repeating units derived from alkyl vinyl ethers, and repeating units derived from vinyl esters of monocarboxylic acids having 3 or more carbon atoms, as described later. One preferred example of the above N-vinyl type monomer is N-vinylpyrrolidone. One preferred example of the above N-(meth)acryloyl type monomer is N-(meth)acryloylmorpholine. The above alkyl vinyl ether may be, for example, propyl vinyl ether, butyl vinyl ether, 2-ethylhexyl vinyl ether, or other vinyl ethers having an alkyl group with 1 to 10 carbon atoms. The above vinyl ester of monocarboxylic acid having 3 or more carbon atoms may be, for example, vinyl propanoate, vinyl butanoate, vinyl pentanoate, vinyl hexanoate, or other vinyl esters of monocarboxylic acids having 3 to 7 carbon atoms.

[0042] A polymer having structural units derived from vinyl alcohol may be a modified PVA comprising VA units and non-VA units having at least one structure selected from oxyalkylene groups, carboxyl groups, sulfo groups, amino groups, hydroxyl groups, amide groups, imide groups, nitrile groups, ether groups, ester groups, and salts thereof.

[0043] A polymer having structural units derived from vinyl alcohol may be a modified PVA in which some of the VA units contained in the polymer having structural units derived from vinyl alcohol are acetalized with an aldehyde compound or a ketone compound. In a preferred embodiment of the art disclosed herein, the acetalized modified PVA is a polymer obtained by the acetalization reaction of the above-mentioned unmodified PVA with an aldehyde compound.

[0044] In one embodiment of the present invention, the aldehyde compound used to produce acetalized modified PVA is not particularly limited. In one preferred embodiment, the aldehyde compound has 1 to 7 carbon atoms, more preferably 2 to 7.

[0045] Examples of the above-mentioned aldehyde compounds include formaldehyde; linear or branched alkylaldehydes such as acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, t-butyraldehyde, and hexylaldehyde; and alicyclic or aromatic aldehydes such as cyclohexanecarbaldehyde and benzaldehyde. These may be used individually or in combination of two or more. In addition, except for formaldehyde, one or more hydrogen atoms may be substituted with halogens or the like. Among these, linear or branched alkylaldehydes are preferred due to their high solubility in water and ease of acetalization reaction, and among these, acetaldehyde, n-propylaldehyde, n-butyraldehyde, and n-pentylaldehyde are more preferred.

[0046] In addition to the above, other aldehyde compounds with 8 or more carbon atoms, such as 2-ethylhexylaldehyde, nonylaldehyde, and decylaldehyde, may also be used as aldehyde compounds.

[0047] Furthermore, as a polymer having structural units derived from vinyl alcohol, a cation-modified polyvinyl alcohol in which a cationic group such as a quaternary ammonium structure has been introduced may be used. Examples of the above-mentioned cation-modified polyvinyl alcohol include those into which a cationic group derived from a monomer having a cationic group, such as diallyldialkylammonium salt or N-(meth)acryloylaminoalkyl-N,N,N-trialkylammonium salt has been introduced.

[0048] The ratio of moles of VA units to the total number of moles of repeating units constituting a polymer having structural units derived from vinyl alcohol may be, for example, 5% or more, 10% or more, 20% or more, or 30% or more. While not particularly limited, in some embodiments, the ratio of moles of VA units may be 50% or more, 65% or more, 75% or more, 80% or more, or 90% or more (e.g., 95% or more, or 98% or more). It is also possible that substantially 100% of the repeating units constituting a polymer having structural units derived from vinyl alcohol are VA units. Here, "substantially 100%" means that, at least intentionally, the polymer having structural units derived from vinyl alcohol does not contain non-VA units, and typically includes cases where the ratio of moles of non-VA units to the total number of moles of repeating units is less than 2% (e.g., less than 1%), and is 0%. In some other embodiments, the ratio of moles of VA units to the total number of moles of repeating units constituting a polymer having structural units derived from vinyl alcohol may be, for example, 95% or less, 90% or less, 80% or less, or 70% or less.

[0049] The content of VA units (by mass) in a polymer having structural units derived from vinyl alcohol may be, for example, 5% by mass or more, 10% by mass or more, 20% by mass or more, or 30% by mass or more. Although not particularly limited, in some embodiments, the content of VA units may be 50% by mass or more (e.g., more than 50% by mass), 70% by mass or more, or 80% by mass or more (e.g., 90% by mass or more, or 95% by mass or more, or 98% by mass or more). Substantially 100% by mass of the repeating units constituting the polymer having structural units derived from vinyl alcohol may be VA units. Here, "substantially 100% by mass" means that, at least intentionally, non-VA units are not included as repeating units constituting the polymer having structural units derived from vinyl alcohol, and typically means that the content of non-VA units in the polymer having structural units derived from vinyl alcohol is less than 2% by mass (e.g., less than 1% by mass). In some other embodiments, the content of VA units in a polymer having structural units derived from vinyl alcohol may be, for example, 95% by mass or less, 90% by mass or less, 80% by mass or less, or 70% by mass or less.

[0050] A polymer having structural units derived from vinyl alcohol may contain multiple polymer chains with different VA unit content within the same molecule. Here, a polymer chain refers to a part (segment) that constitutes a portion of a polymer molecule. For example, a polymer having structural units derived from vinyl alcohol may contain polymer chain A, which has a VA unit content higher than 50% by mass, and polymer chain B, which has a VA unit content lower than 50% by mass (i.e., a non-VA unit content higher than 50% by mass), within the same molecule.

[0051] Polymer chain A may contain only VA units as repeating units, or it may contain non-VA units in addition to VA units. The VA unit content in polymer chain A may be 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more. In some embodiments, the VA unit content in polymer chain A may be 95% by mass or more, or 98% by mass or more. Substantially 100% by mass of the repeating units constituting polymer chain A may be VA units.

[0052] Polymer chain B may contain only non-VA units as repeating units, or it may contain VA units in addition to non-VA units. The content of non-VA units in polymer chain B may be 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more. In some embodiments, the content of non-VA units in polymer chain B may be 95% by mass or more, or 98% by mass or more. Substantially 100% by mass of the repeating units constituting polymer chain B may be non-VA units.

[0053] Examples of polymers having structural units derived from vinyl alcohol that contain polymer chain A and polymer chain B in the same molecule include block copolymers and graft copolymers containing these polymer chains. The above graft copolymer may be a graft copolymer in which polymer chain B (side chain) is grafted onto polymer chain A (main chain), or a graft copolymer in which polymer chain A (side chain) is grafted onto polymer chain B (main chain). In one embodiment, a polymer having structural units derived from vinyl alcohol in which polymer chain B is grafted onto polymer chain A can be used.

[0054] Examples of polymer chain B include polymer chains whose main repeating units are derived from N-vinyl type monomers, polymer chains whose main repeating units are derived from N-(meth)acryloyl type monomers, and polymer chains whose main repeating units are oxyalkylene units. In this specification, unless otherwise specified, the main repeating unit refers to a repeating unit present in an amount exceeding 50% by mass.

[0055] One preferred example of polymer chain B is a polymer chain whose main repeating unit is an N-vinyl type monomer, i.e., an N-vinyl polymer chain. The content of repeating units derived from N-vinyl type monomers in the N-vinyl polymer chain is typically more than 50% by mass, may be 70% by mass or more, 85% by mass or more, or 95% by mass or more. Substantially all of polymer chain B may consist of repeating units derived from N-vinyl type monomers.

[0056] In this specification, examples of N-vinyl type monomers include monomers having a nitrogen-containing heterocyclic ring (e.g., a lactam ring) and N-vinyl chain amides. Specific examples of N-vinyl lactam type monomers include N-vinylpyrrolidone, N-vinylpiperidone, N-vinylmorpholinone, N-vinylcaprolactam, N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholindione. Specific examples of N-vinyl chain amides include N-vinylacetamide, N-vinylpropionic acid amide, and N-vinylbutyric acid amide. Polymer chain B may be an N-vinyl polymer chain in which more than 50% by mass (e.g., 70% or more by mass, or 85% or more by mass, or 95% or more by mass) of its repeating units are N-vinylpyrrolidone units. Substantially all of the repeating units constituting polymer chain B may be N-vinylpyrrolidone units.

[0057] Another example of polymer chain B is a polymer chain whose main repeating unit is an N-(meth)acryloyl type monomer, i.e., an N-(meth)acryloyl polymer chain. The content of repeating units derived from N-(meth)acryloyl type monomers in an N-(meth)acryloyl polymer chain is typically more than 50% by mass, may be 70% by mass or more, 85% by mass or more, or 95% by mass or more. It is also possible that substantially all of polymer chain B consists of repeating units derived from N-(meth)acryloyl type monomers.

[0058] In this specification, examples of N-(meth)acryloyl type monomers include chain amides having an N-(meth)acryloyl group and cyclic amides having an N-(meth)acryloyl group. Examples of chain amides having an N-(meth)acryloyl group include (meth)acrylamides; N-alkyl(meth)acrylamides such as N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and Nn-butyl(meth)acrylamide; and N,N-dialkyl(meth)acrylamides such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, and N,N-di(n-butyl)(meth)acrylamide. Examples of cyclic amides having an N-(meth)acryloyl group include N-(meth)acryloylmorpholine and N-(meth)acryloylpyrrolidine.

[0059] Another example of polymer chain B is a polymer chain containing oxyalkylene units as the main repeating units, i.e., an oxyalkylene polymer chain. The oxyalkylene unit content in the oxyalkylene polymer chain is typically more than 50% by mass, may be 70% or more by mass, 85% or more by mass, or 95% or more by mass. Substantially all of the repeating units contained in polymer chain B may be oxyalkylene units.

[0060] Examples of oxyalkylene units include oxyethylene units, oxypropylene units, and oxybutylene units. Each of these oxyalkylene units may be a repeating unit derived from the corresponding alkylene oxide. The oxyalkylene polymer chain may contain one type of oxyalkylene unit or two or more types. For example, it may be an oxyalkylene polymer chain containing a combination of oxyethylene units and oxypropylene units or butylene oxide units. In an oxyalkylene polymer chain containing two or more types of oxyalkylene units, these oxyalkylene units may be random copolymers of the corresponding alkylene oxides, block copolymers, or graft copolymers. Among these, block copolymers of oxyethylene units and oxypropylene units or random copolymers of oxyethylene units and oxypropylene units are preferred. Block copolymers of oxyethylene units and oxypropylene units may be diblock copolymers, triblock copolymers, etc., containing polyethylene oxide (PEO) blocks and polypropylene oxide (PPO) blocks. Examples of the above triblock copolymers include PEO-PPO-PEO type triblock copolymers and PPO-PEO-PPO type triblock copolymers. Generally, PEO-PPO-PEO type triblock copolymers are more preferred.

[0061] Further examples of polymer chain B include polymer chains containing repeating units derived from alkyl vinyl ethers (e.g., vinyl ethers having alkyl groups with 1 to 10 carbon atoms), polymer chains containing repeating units derived from monocarboxylate vinyl esters (e.g., vinyl esters of monocarboxylic acids with 3 or more carbon atoms), polymer chains in which some of the VA units are acetalized with aldehydes (e.g., alkylaldehydes having alkyl groups with 1 to 7 carbon atoms), and polymer chains into which cationic groups (e.g., cationic groups having a quaternary ammonium structure) are introduced.

[0062] In the water-soluble polymer raw material disclosed herein, the polymer having structural units derived from vinyl alcohol may be unmodified PVA, modified PVA, or a combination of unmodified PVA and modified PVA. In the embodiment in which unmodified PVA and modified PVA are used in combination, the amount of modified PVA used relative to the total amount of polymer having structural units derived from vinyl alcohol contained in the water-soluble polymer raw material may be, for example, less than 95% by mass, 90% by mass or less, 75% by mass or less, 50% by mass or less, 30% by mass or less, 10% by mass or less, 5% by mass or less, or 1% by mass or less. The water-soluble polymer raw material disclosed herein can preferably be implemented in an embodiment in which only one or more types of unmodified PVA are used as polymers having structural units derived from vinyl alcohol.

[0063] The polymers containing nitrogen atoms are not particularly limited, but include polymers containing N-vinyl type monomer units, imine derivatives, polymers containing N-(meth)acryloyl type monomer units, etc. Examples include poly-N-acryloylmorpholine (PACMO), poly-N-vinylpyrrolidone (PVP), polyhydroxyethylacrylamide (PHEAA), poly-N-vinylimidazole (PVI), poly-N-vinylcarbazole, poly-N-vinylcaprolactam, and poly-N-vinylpiperidine. Among these, poly-N-acryloylmorpholine (PACMO) is preferred from the viewpoint of reducing substrate haze. The types of polymers containing nitrogen atoms may be used individually or in combination of two or more types.

[0064] Among these, from the viewpoint of achieving a more pronounced filterability improvement effect in the present invention, a semi-synthetic polymer compound or a synthetic polymer compound is preferred, and a semi-synthetic polymer compound is more preferred. In one embodiment of the present invention, the raw material water-soluble polymer is preferably composed of a hydroxyl group or an ether group from the viewpoint of improving surface quality, and is more preferably a cellulose derivative, and even more preferably hydroxyethylcellulose (HEC).

[0065] As mentioned above, the weight-average molecular weight (Mw) of the raw material water-soluble polymer is not particularly limited as long as it is 2,000 or more. From the viewpoint of making the filterability improvement effect of the present invention more pronounced, it is preferably 10,000 or more, and more preferably 100,000 or more. Furthermore, from the viewpoint of filterability, the weight-average molecular weight (Mw) of the raw material water-soluble polymer is preferably 4,000,000 or less, more preferably 3,000,000 or less, even more preferably 2,800,000 or less, and particularly preferably 1,500,000 or less. Furthermore, the degree of dispersion of the raw material water-soluble polymer (also expressed herein as "Mw / Mn": where Mw represents the weight-average molecular weight and Mn represents the number-average molecular weight) is not particularly limited, but the larger the value, the greater the effect of the present invention tends to be. From this viewpoint, the lower limit of Mw / Mn of the raw material water-soluble polymer is preferably greater than 5, more preferably 10 or more, even more preferably 15 or more, and even more preferably 20 or more. The upper limit of the Mw / Mn ratio of the raw material water-soluble polymer is preferably 95 or less, more preferably 90 or more, even more preferably 85 or more, and even more preferably 80 or more. The upper limit of the Mw / Mn ratio of the raw material water-soluble polymer can be, for example, 75 or less or 40 or less. The weight-average molecular weight (Mw) and number-average molecular weight (Mn) can be measured by gel permeation chromatography (GPC), and details of the measurement method are described in the examples.

[0066] According to one embodiment of the present invention, the raw material water-soluble polymer is a polymer having structural units derived from vinyl alcohol. The weight-average molecular weight (Mw) of the polymer having structural units derived from vinyl alcohol is preferably 2,000 or more, and preferably 2,500 or more. It is more preferable that the weight average molecular weight (Mw) of the polymer having structural units derived from polyvinyl alcohol is preferably 500,000 or less, more preferably 300,000 or less, more preferably 200,000 or less, and more preferably 150,000 or less. According to this embodiment, the filterability is improved.

[0067] According to one embodiment of the present invention, the raw material water-soluble polymer is a cellulose derivative. The weight-average molecular weight (Mw) of the cellulose derivative is preferably 2,000 or more, more preferably 10,000 or more, even more preferably 100,000 or more, for example, it may be 150,000 or more, or 200,000 or more. In some embodiments, it is also preferably 350,000 or more, even more preferably 500,000 or more, even more preferably 700,000 or more, and particularly preferably 900,000 or more, for example, it may be 1,250,000 or more. According to such embodiments, there is a technical effect of improving the surface quality after the polishing and / or rinsing process. According to one embodiment of the present invention, the weight-average molecular weight (Mw) of the cellulose derivative is preferably 4,000,000 or less, more preferably 3,000,000 or less, even more preferably 2,800,000 or less, even more preferably 1,500,000 or less, and particularly preferably 1,000,000 or less. For example, it may be 750,000 or less, or 450,000 or less. According to this embodiment, the filterability is improved.

[0068] According to one embodiment of the present invention, the raw material water-soluble polymer is a polymer having nitrogen atoms. The weight-average molecular weight (Mw) of the polymer having nitrogen atoms is preferably 2,000 or more, more preferably 4,000 or more, even more preferably 10,000 or more, and even more preferably 20,000 or more. According to this embodiment, there is a technical effect of improving the surface quality after the polishing and / or rinsing process. According to one embodiment of the present invention, the weight-average molecular weight (Mw) of the raw material water-soluble polymer having nitrogen atoms is preferably 1,600,000 or less, more preferably 1,250,000 or less, even more preferably 750,000 or less, and even more preferably 400,000 or less. According to this embodiment, the filterability is improved.

[0069] The weight-average molecular weight (Mw), number-average molecular weight (Mn), and molecular weight distribution of water-soluble polymers can be measured by gel permeation chromatography (GPC), specifically employing the method described in the examples.

[0070] According to one embodiment of the present invention, the content of the raw material water-soluble polymer in the dissolution step is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more, from the viewpoint of grinding efficiency in the grinding step. In one embodiment of the present invention, the content of the raw material water-soluble polymer in the dissolution step is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less, from the viewpoint of solubility.

[0071] In one embodiment of the present invention, it is preferable to use a powder as the water-soluble polymer raw material.

[0072] The raw material water-soluble polymer may be used alone or in combination of two or more types, but it is preferable to use one type alone.

[0073] (solvent) In this specification, "solvent" refers to a solvent or dispersion medium. The solvent is not particularly limited as long as it can dissolve the raw material water-soluble polymer, but it is preferable that it contains water. The water content in the solvent is not particularly limited, but it is preferably 50% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass (water only) relative to the total mass of the solvent. As for the water, it is preferable that it contains as few impurities as possible from the viewpoint of preventing contamination of the substrate or interference with the action of other components. For example, it is preferable that the total content of transition metal ions is 100 ppb or less. Here, the purity of the water can be increased by operations such as removal of impurity ions using ion exchange resin, removal of foreign matter by filtration, and distillation. Specifically, as the water, it is preferable to use, for example, deionized water (ion-exchanged water), pure water, ultrapure water, or distilled water.

[0074] Furthermore, the solvent may be an organic solvent or a mixed solvent of water and an organic solvent, as long as it can improve the solubility of the raw material water-soluble polymer. The organic solvent is not particularly limited, and any known organic solvent can be used. When a mixed solvent of water and an organic solvent is used, organic solvents that are miscible with water, such as acetone, acetonitrile, ethanol, methanol, isopropanol, glycerin, ethylene glycol, and propylene glycol, are preferably used. When using an organic solvent, the water and the organic solvent may be mixed, and each component may be added to the resulting mixed solvent and dissolved, or these organic solvents may be used without mixing with water to dissolve the raw material water-soluble polymer, and then mixed with water. These organic solvents can be used individually or in combination of two or more.

[0075] The dissolution method in the dissolution process is not particularly limited as long as it can dissolve the raw material water-soluble polymer in the solvent, but a method of adding the raw material water-soluble polymer to the solvent and stirring is preferred. The stirring method is not particularly limited, and known methods can be used as appropriate. The stirring temperature is not particularly limited, but generally 10 to 40°C is preferred. The stirring time is also not particularly limited.

[0076] [Collision process] The water-soluble polymer of the present invention is a water-soluble polymer processed by a method that includes a step of applying pressure to solutions obtained through the above-described dissolution step by causing them to collide with each other (collision step). In the collision step, two or more solutions collide with each other, resulting in pressure being applied to these solutions. The apparatus for applying pressure to the solutions is not particularly limited, and known apparatus can be used. A preferred example is a jet mill.

[0077] A jet mill is a device that atomizes particles of a material to be processed by collisions between particles of the material being processed or between particles and the flow path wall within a liquid phase flow. More specifically, it is a general term for a device that generates a high-speed flow by any method, causing collisions between the liquids being processed or between the liquids being processed and the flow path wall, and effectively utilizing the turbulence, shear, and cavitation effects generated by the high-speed flow to atomize the raw materials in the liquid being processed and promote dispersion. Typical examples include a method in which the liquid to be processed is ejected from a nozzle using a plunger pump or rotary pump and collides at high speed with a fixed plate, and a method in which the ejected liquids being processed collide head-on with each other. As the liquids being processed pass through the nozzle in the flow path at high speed, or while colliding, they are subjected to turbulence and shear, and when the pressure is released immediately after the collision, a cavitation effect occurs, and the raw materials in the liquid being processed are significantly atomized due to the shock caused by the rapid release of pressure. In this invention, the method in which the ejected liquids being processed collide head-on with each other is used. This prevents the inclusion of impurities.

[0078] Jetmill excels in the selective removal of high molecular weight polymers from raw water-soluble polymers. Here, the selective removal of high molecular weight polymers means that all of the following conditions are met: (1) the amount of high molecular weight polymers is reduced, (2) the amount of low molecular weight polymers is maintained, and (3) the peak-top molecular weight (peak-top molecular weight: Mp) in the differential molecular weight distribution curve described later is maintained. As a result, the filterability of solutions containing the water-soluble polymer to be treated, as well as polishing compositions and / or semiconductor wetting agents, is improved, and the number of defects (LPD-N, LPD, etc.) in substrates polished and / or rinsed with the polishing composition and / or semiconductor wetting agent can be further reduced.

[0079] The jet mill is not particularly limited, and known technologies such as those described in Japanese Patent Publication No. 2015-188853 can be used. Alternatively, commercially available devices such as the Starburst Lab (manufactured by Sugino Machine Co., Ltd.) can be used.

[0080] The processing conditions for a jet mill are not particularly limited, as they vary depending on the equipment used. They can be adjusted as appropriate depending on the object being impacted and the desired selective removal effect of high molecular weight materials after the impact process.

[0081] For example, the processing pressure is not particularly limited, but is preferably 5 MPa or higher, more preferably 10 MPa or higher, even more preferably 15 MPa or higher, and even more preferably 20 MPa or higher. For example, it may be 30 MPa or higher, 40 MPa or higher, 50 MPa or higher, 100 MPa or higher, or 200 MPa or higher. Within this range, the selective removal effect of high molecular weight substances is higher. In addition, the filterability of solutions containing the water-soluble polymer to be processed, polishing compositions, and / or semiconductor wetting agents is further improved. Furthermore, although the processing pressure is not particularly limited, it is preferably 900 MPa or lower, more preferably 500 MPa or lower, and even more preferably 250 MPa or lower. Within this range, the amount of low molecular weight substances is maintained, and the change in peak top molecular weight (Mp) is smaller.

[0082] Furthermore, while there are no particular limitations on the processing time, it is preferably 1 minute or more, more preferably 10 minutes or more, even more preferably 20 minutes or more, and even more preferably 30 minutes or more. For example, it may be 40 minutes or more, 80 minutes or more, or 100 minutes or more. Within this range, the selective removal effect of high molecular weight substances is higher. In addition, the filterability of solutions containing the water-soluble polymer to be processed, polishing compositions, and / or semiconductor wetting agents is further improved. Furthermore, while there are no particular limitations on the processing time, it is preferably 600 minutes or less, more preferably 500 minutes or less, and even more preferably 400 minutes or less. For example, it may be 300 minutes or less, 200 minutes or less, or 150 minutes or less. Within this range, the amount of low molecular weight substances is maintained, and the change in peak top molecular weight (Mp) is smaller.

[0083] Furthermore, while there are no particular restrictions on the flow rate of the processing solution, it is preferably 10 mL / min or more, more preferably 50 mL / min or more, and even more preferably 80 mL / min or more. Within this range, the selective removal effect of high molecular weight substances is higher. Also, the filterability of solutions containing the water-soluble polymer to be processed, polishing compositions, and / or semiconductor wetting agents is further improved. Furthermore, the flow rate of the processing solution is preferably 100,000 mL / min or less, more preferably 10,000 mL / min or less, even more preferably 1,000 mL / min or less, even more preferably 800 mL / min or less, and particularly preferably 600 mL / min or less. Within this range, the amount of low molecular weight substances is maintained, and the change in peak top molecular weight (Mp) is smaller.

[0084] Furthermore, while there are no particular restrictions on the number of treatments, for example, it may be one or more times, preferably three or more times, and more preferably five or more times. Within this range, the selective removal effect of high molecular weight substances is higher. In addition, the filterability of solutions containing the water-soluble polymer to be treated, polishing compositions, and / or semiconductor wetting agents is further improved. Furthermore, the number of treatments is preferably 20 times or less, more preferably 10 times or less, and even more preferably 8 times or less. Within this range, the amount of low molecular weight substances is maintained, and the change in peak top molecular weight (Mp) is smaller.

[0085] (Water-soluble polymer to be treated) As mentioned above, the water-soluble polymer to be treated is preferably one from which high molecular weight components of the raw water-soluble polymer have been selectively removed by the collision process. Furthermore, it is preferable that the amount of low molecular weight components is maintained and that the change in peak top molecular weight (Mp) is smaller.

[0086] In this specification, a high molecular weight component refers to a component with a molecular weight higher than the peak-top molecular weight (Mp). More specifically, in the differential molecular weight distribution curve of a water-soluble polymer, it refers to a component corresponding to a LogM on the higher molecular weight side than the LogM at which dw / d(LogM) becomes the peak.

[0087] Furthermore, in this specification, a low molecular weight component refers to a component with a molecular weight lower than the peak-top molecular weight (Mp). More specifically, in the differential molecular weight distribution curve of a water-soluble polymer, it refers to a component corresponding to a LogM on the lower molecular weight side than the LogM at which dw / d(LogM) is the peak.

[0088] The water-soluble polymer to be treated in the present invention is not particularly limited, but it is preferable that it has at least one of the following characteristics [1] to [3], in that high molecular weight components of the raw water-soluble polymer are selectively removed. Furthermore, it is preferable that the water-soluble polymer has two or more of the following characteristics [1] to [3], and it is more preferable that it has all of the characteristics.

[0089] [1] Decrease in the amount of high molecular weight substances The change in the amount of high molecular weight in the treated water-soluble polymer can be confirmed as follows: (1) Plot the differential molecular weight distribution curves of the raw water-soluble polymer and the treated water-soluble polymer. (2) When the value of dw / d(LogM) on the vertical axis is 20, extract the larger of the two values ​​of LogM on the horizontal axis, namely LogM(R) and LogM(P). (3) Compare the LogM(P) of the treated water-soluble polymer with the LogM(R) of the raw water-soluble polymer. If LogM(P) is smaller than LogM(R), it can be said that the amount of high molecular weight has decreased.

[0090] Since a larger reduction in high molecular weight is preferable, a smaller LogM(P) / LogM(R) ratio (the ratio of LogM(P) to LogM(R)) (%) is preferable. This ratio is preferably 98% or less, more preferably 85% or less, even more preferably 80% or less, even more preferably 65% ​​or less, particularly preferably 60% or less, and even more preferably 45% or less. When this ratio is within the above range, the polishing composition and / or semiconductor wetting agent according to the present invention is densely adsorbed to the wafer, thereby further reducing surface defects. This ratio can be lowered by increasing the pressure applied to the solution in the impact process. In jet milling, for example, this ratio can be lowered by increasing the processing pressure.

[0091] [2] Maintaining the amount of low molecular weight products The change in the amount of low molecular weight components in the water-soluble polymer being treated can be confirmed as follows: (1) Plot the differential molecular weight distribution curves of the raw water-soluble polymer and the water-soluble polymer being treated. (2) Extract the dw / d(LogM) values ​​for the raw water-soluble polymer and the water-soluble polymer being treated, respectively, when the LogM value on the horizontal axis is 4.5. (3) Compare the dw / d(LogM(p)) of the water-soluble polymer being treated with the dw / d(LogM(r)) of the water-soluble polymer being treated. If the difference between dw / d(LogM(p)) and dw / d(LogM(r)) is small, it can be said that the amount of low molecular weight components is maintained.

[0092] Since a small change in the amount of low molecular weight material is preferable, the ratio of [dw / d(LogM(p))] / [dw / d(LogM(r))] (the ratio of dw / d(LogM(p)) to dw / d(LogM(r))) (%) is preferable as close to 100% as possible. The range may be, for example, 100±5%, preferably 100±3%, more preferably 100±2%, even more preferably 100±1%, even more preferably 100±0.8%, particularly preferably 100±0.5%, even more preferably 100±0.3%, and extremely preferably 100±0.1%. When the ratio is within the above range, it is considered that the function of densely protecting the wafer, which is exhibited by the low molecular weight material of the water-soluble polymer raw material, can be maintained. Therefore, surface defects can be further reduced when polishing with the polishing composition and / or semiconductor wetting agent containing the water-soluble polymer to be treated according to the present invention.

[0093] [3] Maintaining the peak-top molecular weight (Mp) The change in the peak top molecular weight (Mp) of the water-soluble polymer being treated can be confirmed as follows: (1) Plot the differential molecular weight distribution curves of the raw water-soluble polymer and the water-soluble polymer being treated. (2) Extract the LogM peaks for dw / d(LogM) from each. (3) Compare the LogM(p_peak) of the water-soluble polymer being treated with the LogM(r_peak) of the raw water-soluble polymer. Here, if the difference between LogM(p_peak) and LogM(r_peak) is small, it can be said that the change in the peak top molecular weight (Mp) is small.

[0094] Since a smaller change in peak-top molecular weight (Mp) is preferable, the ratio of LogM(p_peak) / LogM(r_peak) (the ratio of LogM(p_peak) to LogM(r_peak)) (%) is preferable as close to 100% as possible. The range is, for example, preferably 100±5%, more preferably 100±4%, even more preferably 100±3%, even more preferably 100±2%, particularly preferably 100±1.5%, even more particularly preferably 100±1%, extremely preferably 100±0.5%, and even more extremely preferably 100±0.1%. When the ratio is within the above range, it is considered that the function of protecting the wafer more uniformly can be maintained. Therefore, surface defects can be further reduced when polishing with the polishing composition and / or semiconductor wetting agent containing the above-mentioned water-soluble polymer to be treated according to the present invention.

[0095] The differential molecular weight distribution curve of polymers can be prepared using general methods, and details of the preparation method are described in the examples. Furthermore, the GPC dissolution curve obtained by measurement using the GPC method, and the calculation of the area in the differential molecular weight distribution curve, can be performed using the analysis software installed on the GPC instrument (Tosoh Corporation, product name "HLC-8420 GPC").

[0096] In addition to the specifications described in [1] to [3] above, the water-soluble polymer to be treated has the following characteristics.

[0097] The Mw / Mn ratio of the water-soluble polymer to be treated is not particularly limited, but is preferably 30 or less, more preferably 25 or less, even more preferably 20 or less, even more preferably 15 or less, particularly preferably 10 or less, and even more preferably 8 or less. For example, it may be 7.5 or less (typically 7 or less). Within this range, the number of defects (e.g., LPD-N and LPD) in the substrate polished with the polishing composition and / or semiconductor wetting agent containing the water-soluble polymer to be treated can be further reduced. Furthermore, the solution, polishing composition, and / or semiconductor wetting agent containing the water-soluble polymer to be treated has better filterability. In addition, the Mw / Mn ratio of the water-soluble polymer to be treated is preferably 1 or more.

[0098] The ratio (%) of the dispersion degree (Mw / Mn) of the water-soluble polymer to be treated to the dispersion degree (Mw / Mn) of the raw material water-soluble polymer is preferably low. The above ratio is not particularly limited, but is preferably 90% or less, more preferably 80% or less, even more preferably 75% or less, even more preferably 70% or less, particularly preferably 30% or less, even more preferably 25% or less, and extremely preferably 20% or less. The smaller the ratio, the narrower the molecular weight distribution, indicating that a water-soluble polymer to be treated with a more uniform weight molecular weight is obtained. Furthermore, the ratio is preferably 1% or more, more preferably 5% or more, even more preferably 10% or more, and particularly preferably 15% or more. When the ratio is within the above range, the amount of low molecular weight material tends to be maintained. Also, when the ratio is within the above range, the particle size of the raw material water-soluble polymer becomes more uniform, and the wafer can be protected more densely. Therefore, surface defects can be further reduced when polishing and / or rinsing with a polishing composition and / or semiconductor wetting agent containing the above water-soluble polymer to be treated. This proportion can be reduced by increasing the pressure applied to the solution during the impact process. In jet milling, for example, this proportion can be reduced by increasing the processing pressure.

[0099] The water-soluble polymer obtained through the collision process has the advantage of having a small difference in the amount of impurities between the treated water-soluble polymer and the raw water-soluble polymer. In particular, the difference in the amount of metal impurities is small. This is thought to be because the collision process involves colliding solutions with each other and applying pressure to the solutions, and does not involve collisions with other materials, thus making it difficult for impurities to be introduced. The amount of metal impurities can be evaluated by measuring the metal impurity concentration using inductively coupled plasma (ICP) emission spectrometry. For example, the inductively coupled high-frequency plasma spectrometer "ICP-AES" manufactured by Shimadzu Corporation can be used as the measuring device. Depending on the type of metal impurity, inductively coupled plasma mass spectrometer (ICP-MS) or atomic absorption spectrometer may also be used.

[0100] ≪Method for producing polishing compositions and semiconductor wetting agents≫ One embodiment of the present invention relates to a method for producing an abrasive composition comprising abrasive grains and a water-soluble polymer (water-soluble polymer to be treated), comprising the steps of: dissolving a raw material water-soluble polymer in a solvent to make a solution (dissolution step); colliding the solutions with each other and applying pressure to the solution (collision step); and mixing abrasive grains into the pressurized solution.

[0101] Another embodiment of the present invention relates to a method for producing a semiconductor wetter comprising a water-soluble polymer (water-soluble polymer to be treated), comprising a dissolution step, a collision step, and a step of mixing other components into the pressurized solution.

[0102] In these forms, the water-soluble polymer to be treated is the one described in the above sections on the treatment of the water-soluble polymer and the water-soluble polymer to be treated. Furthermore, the dissolution step and collision step are the same as those described in the above sections on the treatment of the water-soluble polymer and the water-soluble polymer to be treated.

[0103] Furthermore, the method for producing a polishing composition and / or a semiconductor wetting agent according to one embodiment of the present invention may include a plurality of mixing steps, in which case other steps may be included between each mixing step. For example, a filtration step, described later, may be provided after a mixing step for one component, and then a mixing step for another component, described later, may be provided thereafter.

[0104] [Mixing process] The polishing composition of the present invention is manufactured by a method comprising a step of mixing (mixing step) the solution obtained through the above-mentioned impact step with other components, including at least abrasive grains. Here, the other components are components other than the water-soluble polymer to be treated obtained from the raw material water-soluble polymer through the above-mentioned dissolution step and impact step, and the solvent used in the above-mentioned dissolution step and impact step. Examples of other components include various components used in known polishing compositions, such as basic compounds, organic acids or their salts, inorganic acids or their salts, surfactants, chelating agents, preservatives, antifungal agents, water-soluble polymers other than the water-soluble polymer to be treated, and dispersants. These other components can be mixed insofar as the effects of the present invention are not significantly hindered. An example of other components including at least abrasive grains is, for example, only abrasive grains.

[0105] Furthermore, the semiconductor wetting agent of the present invention is manufactured by a method that includes a step (mixing step) of mixing the above-mentioned other components into the solution obtained through the above-mentioned collision step, without mixing in abrasive particles.

[0106] The mixing method and conditions for the various components in the mixing process are not particularly limited. For example, the various components may be added to the solution obtained through the collision process, or the solution obtained through the collision process may be added to the various components. The order in which the various components are added is also not particularly limited; they may be added simultaneously, sequentially, or only some components may be added simultaneously. The mixing temperature is not particularly limited, but generally 10 to 40°C is preferred, and heating may be used to increase the dissolution rate. The mixing time is also not particularly limited. The mixing apparatus is also not particularly limited. For example, well-known mixing apparatuses such as vane stirrers, ultrasonic dispersers, and homomixers can be used.

[0107] The following describes the various components added during the mixing process.

[0108] (Abrasive grains) The material and properties of the abrasive particles are not particularly limited and can be appropriately selected according to the purpose and manner of use of the polishing composition. Examples of abrasive particles include inorganic particles, organic particles, and organic-inorganic composite particles. Specific examples of inorganic particles include oxide particles such as silica particles, alumina particles, cerium oxide particles, chromium oxide particles, titanium dioxide particles, zirconium oxide particles, magnesium oxide particles, manganese dioxide particles, zinc oxide particles, and red iron oxide particles; nitride particles such as silicon nitride particles and boron nitride particles; carbide particles such as silicon carbide particles and boron carbide particles; diamond particles; and carbonates such as calcium carbonate and barium carbonate. Specific examples of organic particles include polymethyl methacrylate (PMMA) particles, poly(meth)acrylic acid particles, and polyacrylonitrile particles. Here, (meth)acrylic acid refers comprehensively to acrylic acid and methacrylic acid. Such abrasive particles may be used individually or in combination of two or more types. Note that semiconductor wetting agents do not contain abrasive particles.

[0109] As the abrasive grains, inorganic particles are preferred, and among these, particles made of metal or metalloid oxides are preferred, with silica particles being particularly preferred. In polishing compositions that can be used for polishing substrates having a silicon surface, such as silicon wafers described later, for example, for finish polishing, it is particularly significant to use silica particles as abrasive grains. The technology disclosed herein can preferably be implemented, for example, in a form in which the abrasive grains consist substantially of silica particles. Here, "substantially" means that 95% by mass or more of the particles constituting the abrasive grains are silica particles. 98% by mass or more, preferably 99% by mass or more, for example, 100% by mass of the particles constituting the abrasive grains may be silica particles.

[0110] Specific examples of silica particles include colloidal silica, fumed silica, and precipitated silica. Silica particles can be used individually or in combination of two or more types. Colloidal silica is particularly preferred because it easily yields a polished surface with excellent surface quality after polishing. As colloidal silica, for example, colloidal silica produced from water glass (sodium silicate) by ion exchange or colloidal silica produced by the alkoxide method can be preferably used. Here, colloidal silica produced by the alkoxide method refers to colloidal silica produced by the hydrolysis condensation reaction of alkoxysilane. Colloidal silica can be used individually or in combination of two or more types.

[0111] The true specific gravity of the abrasive grain constituent material is preferably 1.5 or higher, and more preferably 1.6 or higher. The abrasive grain constituent material is, for example, silica that constitutes silica particles. As the true specific gravity of the abrasive grain constituent material increases, the physical polishing ability tends to increase. When the physical polishing ability of the abrasive grains increases, the local stress that the abrasive grains exert on the substrate surface tends to increase in general. From this viewpoint, abrasive grains with a true specific gravity of 1.7 or higher are particularly preferred. There is no particular upper limit to the true specific gravity of the abrasive grains, but it is typically 2.3 or lower, for example, 2.2 or lower. The true specific gravity of the abrasive grains (e.g., silica particles) can be measured using a liquid displacement method with ethanol as the displacement solution.

[0112] The average primary particle diameter (BET diameter) of the abrasive grains is not particularly limited, but from the viewpoint of polishing efficiency, it is preferably 5 nm or more, more preferably 10 nm or more, and even more preferably 15 nm or more. From the viewpoint of obtaining a higher polishing effect, such as reduction of haze and removal of defects, the BET diameter is preferably 15 nm or more, more preferably 20 nm or more, for example, more preferably greater than 20 nm. From the viewpoint of suppressing local stress that the abrasive grains impart to the substrate surface, the average primary particle diameter of the abrasive grains is preferably 100 nm or less, more preferably 80 nm or less, and even more preferably 60 nm or less. The technology disclosed herein can also be preferably implemented using abrasive grains with an average primary particle diameter of 50 nm or less, typically less than 40 nm, more preferably 35 nm or less, and even more preferably 32 nm or less, as it is easier to obtain a higher quality surface.

[0113] The average primary particle size of abrasive grains is calculated, for example, from the specific surface area measured by the BET method. The specific surface area of ​​abrasive grains can be measured, for example, using the "Flow SorbII 2300" manufactured by Micromeritex. In this specification, the BET diameter is calculated from the specific surface area (BET value) measured by the BET method as follows: BET diameter (nm) = 6000 / (true density (g / cm³) 3 ) × BET value (m 2 This refers to the particle size calculated using the formula ( / g).

[0114] The average secondary particle diameter of the abrasive grains is not particularly limited, but from the viewpoint of polishing efficiency, it is preferably 10 nm or more, more preferably 15 nm or more, even more preferably 20 nm or more, and particularly preferably 25 nm or more. From the viewpoint of obtaining a higher polishing effect, such as reduction of haze and removal of defects, the above average secondary particle diameter is preferably 30 nm or more, and more preferably 40 nm or more. Furthermore, from the viewpoint of suppressing local stress that the abrasive grains impart to the substrate surface, the average secondary particle diameter of the abrasive grains is preferably 300 nm or less, more preferably 200 nm or less, even more preferably 150 nm or less, and even more preferably 125 nm or less. The technology disclosed herein is also preferable in which abrasive grains with an average secondary particle diameter of 100 nm or less, for example, less than 80 nm (typically 45 nm or less) are used, as it is easier to obtain a higher quality surface, and the stability of the polishing composition is improved by the reduction in the average secondary particle diameter of the abrasive grains that can be implemented. The average secondary particle size of the abrasive grains can be measured, for example, by dynamic light scattering using the "UPA-UT151" model manufactured by Nikkiso Co., Ltd.

[0115] The shape (outer form) of the abrasive grains may be spherical or non-spherical. Specific examples of non-spherical particles include peanut-shaped (i.e., the shape of a peanut shell), cocoon-shaped, konpeito-shaped, and rugby ball-shaped particles. For example, abrasive grains in which most of the particles are peanut-shaped can be preferably used.

[0116] While not particularly limited, the average value of the major axis / minor axis ratio of the abrasive grains, i.e., the average aspect ratio, is in principle 1.0 or higher, preferably 1.05 or higher, and more preferably 1.1 or higher. Increasing the average aspect ratio can lead to higher polishing efficiency. Furthermore, from the viewpoint of reducing scratches, the average aspect ratio of the abrasive grains is preferably 3.0 or lower, more preferably 2.0 or lower, and even more preferably 1.5 or lower.

[0117] The shape (outer shape) and average aspect ratio of abrasive grains can be determined, for example, by electron microscopy observation. A specific procedure for determining the average aspect ratio is to use a scanning electron microscope (SEM) to draw the smallest rectangle circumscribing each particle image for a predetermined number of silica particles whose individual particle shapes can be recognized. The predetermined number is, for example, 200 particles. Then, for the rectangle drawn for each particle image, the ratio of the major axis to the minor axis (aspect ratio) is calculated by dividing the length of the major side (major axis) by the length of the minor side (minor axis). The average aspect ratio can be obtained by taking the arithmetic mean of the aspect ratios of the predetermined number of particles.

[0118] (Water-soluble polymer) The polishing composition and / or semiconductor wetting agent of the present invention contains the above-mentioned water-soluble polymer to be treated. The raw material water-soluble polymer of the water-soluble polymer to be treated may contain two or more water-soluble polymers. Preferably, the raw material water-soluble polymer of the water-soluble polymer to be treated is one water-soluble polymer.

[0119] The content of the water-soluble polymer to be treated in the polishing composition and / or semiconductor wetting agent is not particularly limited, but from the viewpoint of surface quality after the polishing and / or rinsing process, it is preferably 0.0001 parts by mass or more, more preferably 0.0005 parts by mass or more, even more preferably 0.001 parts by mass or more, even more preferably 0.0015 parts by mass or more, and particularly preferably 0.002 parts by mass or more, for example, it may be 0.05 parts by mass or more (typically 0.1 parts by mass or more) per 100 parts by mass of solvent. Furthermore, from the viewpoint of filterability, the content of the water-soluble polymer to be treated in the polishing composition and / or semiconductor wetting agent is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 2 parts by mass or less, even more preferably 1 part by mass or less, and particularly preferably 0.5 parts by mass or less, for example, it may be 0.3 parts by mass or less (typically 0.2 parts by mass or less) per 100 parts by mass of solvent.

[0120] The polishing composition and / or semiconductor wetting agent according to one embodiment of the present invention may contain water-soluble polymers other than the treated water-soluble polymer (hereinafter also referred to as "optional polymers") to the extent that the effects of the present invention are not significantly hindered. Examples of optional polymers include the types of water-soluble polymers exemplified in the dissolution step described above. Other water-soluble polymers include polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyisoamylene sulfonic acid, polystyrene sulfonate, polyacrylate, polyvinyl acetate, and the like. The optional polymers can be used individually or in combination of two or more.

[0121] The content of the arbitrary polymer in the polishing composition and / or semiconductor wetting agent is not particularly limited, but may be the content of the water-soluble polymer to be treated as described in the mixing step above. The ratio of the content of the water-soluble polymer to the content of the arbitrary polymer is not particularly limited, but from the viewpoint of surface quality after the polishing step, the ratio of the arbitrary polymer to the total amount of water-soluble polymer is preferably 70% or less, more preferably 60% or less, more preferably 50% or less, even more preferably 40% or less, even more preferably 30% or less, and particularly preferably 20% or less. For example, it may be 10% or less, or 5% or less.

[0122] In one embodiment of the present invention, when the polishing composition and / or semiconductor wetting agent is in a concentrated liquid state, the content of water-soluble polymers in the polishing composition and / or semiconductor wetting agent is preferably 0.0001% by mass or more, more preferably 0.0005% by mass or more, even more preferably 0.001% by mass or more, and particularly preferably 0.01% by mass or more, from the viewpoint of improving stability. In one embodiment of the present invention, when the polishing composition and / or semiconductor wetting agent is in a concentrated liquid state, the content of water-soluble polymers in the polishing composition and / or semiconductor wetting agent is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, from the viewpoint of storage stability and filterability.

[0123] In one embodiment of the present invention, when the polishing composition and / or semiconductor wetting agent is in a diluted state, the content of the water-soluble polymer is preferably 0.00005% by mass or more, more preferably 0.0001% by mass or more, even more preferably 0.0005% by mass or more, and particularly preferably 0.001% by mass or more, from the viewpoint of improving the surface quality after the polishing and / or rinsing process. Furthermore, in one embodiment of the present invention, when the polishing composition and / or semiconductor wetting agent is in a diluted state, the content of the water-soluble polymer is preferably 0.1% by mass or less, more preferably 0.05% by mass or less, and even more preferably 0.01% by mass or less, from the viewpoint of maintaining the polishing rate. In the above, the content of the water-soluble polymer refers to the total amount if the polishing composition and / or semiconductor wetting agent contains two or more types of water-soluble polymers.

[0124] (Dispersant) The dispersion medium contained in the polishing composition and / or semiconductor wetting agent is not particularly limited, but is preferably of the type exemplified in the dissolution step described above. In particular, it is preferable to use the solvent used in the dissolution step and / or the impact step as is. The solvent used in the dissolution step and / or the impact step usually functions as a dispersion medium in the polishing composition and / or semiconductor wetting agent, especially with respect to the abrasive particles.

[0125] (Basic compounds) In this specification, a basic compound refers to a compound that dissolves in water and has the function of increasing the pH of an aqueous solution. Examples of basic compounds include nitrogen-containing organic or inorganic basic compounds, alkali metal hydroxides, alkaline earth metal hydroxides, various carbonates and bicarbonates, etc. Examples of nitrogen-containing basic compounds include quaternary ammonium compounds, quaternary phosphonium compounds, ammonia, and amines. Amines are preferably water-soluble amines. Such basic compounds can be used individually or in combination of two or more.

[0126] Specific examples of alkali metal hydroxides include potassium hydroxide and sodium hydroxide. Specific examples of carbonates or bicarbonates include ammonium bicarbonate, ammonium carbonate, potassium bicarbonate, potassium carbonate, sodium bicarbonate, and sodium carbonate. Specific examples of amines include methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, monoethanolamine, N-(β-aminoethyl)ethanolamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, anhydrous piperazine, piperazine hexahydrate, 1-(2-aminoethyl)piperazine, N-methylpiperazine, guanidine, and azoles such as imidazole and triazole. Specific examples of quaternary phosphonium compounds include quaternary phosphonium hydroxides such as tetramethylphosphonium hydroxide and tetraethylphosphonium hydroxide.

[0127] As the quaternary ammonium compound, quaternary ammonium salts such as tetraalkylammonium salts and hydroxyalkyltrialkylammonium salts can be preferably used. Quaternary ammonium salts are typically strong bases. The anion component in such quaternary ammonium salts is, for example, OH - , F - , Cl - , Br - , I - , ClO4 - , BH4 - and the like. Among them, a preferred example includes a quaternary ammonium salt whose anion is OH - , that is, quaternary ammonium hydroxide. Specific examples of quaternary ammonium hydroxide include tetraalkylammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetrapentylammonium hydroxide and tetrahexylammonium hydroxide; hydroxyalkyltrialkylammonium hydroxides such as 2-hydroxyethyltrimethylammonium hydroxide (also referred to as choline); and the like.

[0128] Among these basic compounds, for example, at least one basic compound selected from alkali metal hydroxides, quaternary ammonium hydroxides and ammonia can be preferably used. Above all, tetraalkylammonium hydroxide and ammonia are more preferred, and ammonia is particularly preferred. Examples of the tetraalkylammonium hydroxide include tetramethylammonium hydroxide.

[0129] When the polishing composition and / or semiconductor wetting agent disclosed herein contains a basic compound, the content of the basic compound in the polishing composition and / or semiconductor wetting agent is not particularly limited. From the viewpoint of suitably treating the substrate surface, it is usually preferable that the content in the concentrated or diluted solution be 0.0001% by mass or more of the polishing solution, more preferably 0.0005% by mass or more, for example 0.001% by mass or more, and typically more preferably 0.002% by mass or more. Furthermore, from the viewpoint of improving surface quality, the content is appropriate to be less than 15% by mass, preferably less than 10% by mass, more preferably less than 5% by mass, even more preferably less than 1.0% by mass, and even more preferably less than 0.5% by mass.

[0130] (Organic acids or their salts, inorganic acids or their salts) Examples of organic acids include fatty acids such as formic acid, acetic acid, and propionic acid; aromatic carboxylic acids such as benzoic acid and phthalic acid; citric acid, oxalic acid, tartaric acid, malic acid, maleic acid, fumaric acid, succinic acid, organic sulfonic acid, and organic phosphonic acid. Examples of organic acid salts include alkali metal salts of organic acids, such as sodium salts, potassium salts, and ammonium salts. Examples of inorganic acids include sulfuric acid, nitric acid, hydrochloric acid, and carbonic acid. Examples of inorganic acid salts include alkali metal salts of inorganic acids, such as sodium salts, potassium salts, and ammonium salts. Organic acids and their salts, as well as inorganic acids and their salts, can be used individually or in combination of two or more.

[0131] (Oxidizing agent) Examples of oxidizing agents include hydrogen peroxide (H2O2), sodium persulfate, ammonium persulfate, and sodium dichloroisocyanurate. It is preferable that the polishing compositions and semiconductor wetting agents disclosed herein are substantially free of oxidizing agents. If an oxidizing agent is present in the polishing composition and / or semiconductor wetting agent, when the polishing composition and / or semiconductor wetting agent is supplied to the object to be polished, the surface of the object is oxidized, forming an oxide film. This can lead to a decrease in the surface quality of the substrate or a decrease in the effectiveness of the polishing composition and / or semiconductor wetting agent on the substrate surface. The substrate is, for example, a silicon wafer. Note that "substantially free of oxidizing agents" in the polishing composition and / or semiconductor wetting agent means that, at the very least, the inclusion of an oxidizing agent is intentional.

[0132] (Surfactants) Any type of surfactant can be used: anionic, cationic, nonionic, or amphoteric. Generally, anionic or nonionic surfactants are preferred. Nonionic surfactants are more preferred from the viewpoint of low foaming and ease of pH adjustment. Examples of nonionic surfactants include oxyalkylene polymers such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; polyoxyalkylene derivatives such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene alkylamines, polyoxyethylene fatty acid esters, polyoxyethylene glyceryl ether fatty acid esters, and polyoxyethylene sorbitan fatty acid esters (e.g., polyoxyalkylene adducts); and copolymers of multiple types of oxyalkylenes (e.g., diblock copolymers, triblock copolymers, random copolymers, alternating copolymers). In one embodiment, a surfactant containing a polyoxyalkylene structure (e.g., a polyoxyethylene structure, a polyoxypropylene structure, etc.) within a single molecule is preferred. Surfactants can be used individually or in combination of two or more.

[0133] (Chelating agent) Examples of chelating agents include aminocarboxylic acid-based chelating agents and organic phosphonic acid-based chelating agents. Examples of aminocarboxylic acid-based chelating agents include ethylenediaminetetraacetic acid, sodium ethylenediaminetetraacetic acid, nitrilotriacetic acid, sodium nitrilotriacetate, ammonium nitrilotriacetate, hydroxyethylethylenediaminetriacetic acid, sodium hydroxyethylethylenediaminetriacetate, diethylenetriaminepentaacetic acid, sodium diethylenetriaminepentaacetate, triethylenetetraminehexaacetic acid, and sodium triethylenetetraminehexaacetate. Examples of organic phosphonic acid chelating agents include 2-aminoethylphosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetrakis(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), ethane-1,1-diphosphonic acid, ethane-1,1,2-triphosphonic acid, ethane-1-hydroxy-1,1-diphosphonic acid, ethane-1-hydroxy-1,1,2-triphosphonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, methanehydroxyphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, 1-phosphonobutane-2,3,4-tricarboxylic acid, and α-methylphosphonosuccinic acid. Of these, organic phosphonic acid chelating agents are more preferred. Among the preferred chelating agents are ethylenediaminetetrakis(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), and diethylenetriaminepentaacetic acid. Particularly preferred chelating agents include ethylenediaminetetrakis(methylenephosphonic acid) and diethylenetriaminepenta(methylenephosphonic acid). The chelating agents can be used individually or in combination of two or more.

[0134] [Filtration process] An abrasive composition and / or semiconductor wetting agent according to one embodiment of the present invention may be manufactured by a method comprising a step of filtering the solution used to manufacture the abrasive composition and / or semiconductor wetting agent (hereinafter also referred to simply as the "filtration step").

[0135] A preferred embodiment of the present invention provides a method for producing a polishing composition and / or a semiconductor wetting agent, further comprising a step of filtering the solution obtained through the collision step after the collision step and before the mixing step. Alternatively, a preferred embodiment of the present invention provides a method for producing a polishing composition and / or a semiconductor wetting agent, further comprising a step of filtering the solution obtained through the mixing step after the mixing step. In addition, a manufacturing method according to one embodiment of the present invention may further include a step of filtering the solution at both of the above timings.

[0136] The material of the filter used in the filtration process is not particularly limited and includes, for example, cellulose mixed esters, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer, polycarbonate, polyethersulfone, cellulose acetate, nitrocellulose, regenerated cellulose, polyamide, triacetylcellulose, polypropylene, polyvinyl chloride (PVC), nylon, nylon 66, polysulfone, polyester, polypropylene / polyethylene, acrylic copolymer, polycarbonate, polylactic acid, polycaprolactone, polyglycolic acid, polydioxanone, polyhydroxybutyrate, polybutadiene, polyurethane, polystyrene (PS), polymethyl methacrylate, resins such as polycarbonate, glass, metal, etc.

[0137] The filter structure is not particularly limited and can include depth structures, pleated structures, membrane structures, etc.

[0138] The pore size of the filter is not particularly limited, but is preferably 0.03 μm or larger, more preferably 0.04 μm or larger, even more preferably 0.05 μm or larger, even more preferably 0.1 μm or larger, and particularly preferably 0.2 μm or larger. A pore size of 0.03 μm or larger, for example 0.04 μm or larger, is preferable because it allows for a high filtration rate. Furthermore, the pore size of the filter is preferably 100 μm or smaller, more preferably 70 μm or smaller, even more preferably 50 μm or smaller, even more preferably 15 μm or smaller, and particularly preferably 1 μm or smaller (specifically, for example, 0.5 μm or smaller is preferable). A pore size of 100 μm or smaller improves the accuracy of filtration.

[0139] The filtration method may be any of the following: natural filtration at atmospheric pressure, suction filtration, pressure filtration, or centrifugal filtration.

[0140] [Other processes] The polishing composition and / or semiconductor wetting agent according to one embodiment of the present invention may be manufactured by further steps other than the dissolution step, the impact step, the mixing step, and the filtration step described above.

[0141] Polishing compositions, semiconductor wetting agents The polishing composition and / or semiconductor wetting agent of the present invention has the following properties.

[0142] (D90) The D90(P) of particles in the polishing composition of the present invention is smaller than the D90(R) of particles in the polishing composition containing the raw material water-soluble polymer that has not been treated according to the present invention. Here, D90 refers to the particle size at which the cumulative mass from the small particle size side of the cumulative particle size distribution on a volume basis becomes 90%. The ratio (%) of D90(P) to D90(R) is not particularly limited, but is preferably 99.5% or less, more preferably 95% or less, and even more preferably 90% or less. When the ratio is within this range, the number of defects (e.g., LPD-N and LPD) in the substrate polished and / or rinsed with the polishing composition and / or semiconductor wetting agent can be further reduced. In addition, the dispersibility of abrasive particles in the polishing composition is improved, and it has better filterability. The ratio is preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more. When the ratio is within this range, it is possible to suppress the reduction in physical processing force (e.g., polishing rate) due to the particle size becoming too small. The D90 of the polishing composition can be determined by dynamic light scattering using the UPA-UT151 manufactured by Nikkiso Co., Ltd., and details of the measurement method are described in the examples.

[0143] (pH) The pH of the polishing composition according to one embodiment of the present invention is preferably 8.0 or higher, more preferably 8.5 or higher, even more preferably 9.0 or higher, even more preferably 9.5 or higher, and particularly preferably 10.0 or higher. As the pH of the polishing composition increases, the polishing efficiency tends to improve. On the other hand, from the viewpoint of preventing the dissolution of abrasive grains and suppressing a decrease in mechanical polishing action, the pH of the polishing composition is preferably 13.0 or lower, more preferably 12.5 or lower, even more preferably 12.0 or lower, even more preferably 11.5 or lower, particularly preferably 11.0 or lower, and even more particularly preferably 10.8 or lower. For example, it may be 10.5 or lower, or 10.0 or lower.

[0144] The pH of the semiconductor wetting agent according to one embodiment of the present invention is preferably 8.0 or higher, more preferably 8.5 or higher, even more preferably 9.0 or higher, even more preferably 9.5 or higher, and particularly preferably 10.0 or higher. Furthermore, the pH of the semiconductor wetting agent is preferably 13.0 or lower, more preferably 12.5 or lower, even more preferably 12.0 or lower, even more preferably 11.5 or lower, particularly preferably 11.0 or lower, and even more particularly preferably 10.8 or lower. For example, it may be 10.5 or lower, or 10.0 or lower. When the pH of the semiconductor wetting agent is within the above range, the surface of the substrate can be suitably treated.

[0145] pH can be determined by using a pH meter, performing a three-point calibration with a standard buffer solution, then placing the glass electrode in the composition to be measured, and measuring the value after it has stabilized for at least two minutes. As a pH meter, for example, LAQUA® manufactured by Horiba, Ltd. or an equivalent product can be used. As standard buffer solutions, phthalate pH buffer pH: 4.01 (25°C), neutral phosphate pH buffer pH: 6.86 (25°C), and carbonate pH buffer pH: 10.01 (25°C) can be used.

[0146] <Methods for polishing and rinsing> One embodiment of the present invention is a method for polishing a substrate using an abrasive composition containing abrasive grains and a water-soluble polymer to be treated. Another embodiment of the present invention is a method for rinsing a substrate using a semiconductor wetting agent containing a water-soluble polymer to be treated.

[0147] In these forms, the abrasive grains are the same as those described in the above-mentioned descriptions of the polishing composition and semiconductor wetting agent manufacturing method. Furthermore, the water-soluble polymer to be treated is the same as those described in the above-mentioned descriptions of the treatment of water-soluble polymers and the water-soluble polymer to be treated.

[0148] A preferred embodiment of a method for polishing and / or rinsing a substrate using the polishing composition and / or semiconductor wetting agent according to the present invention will be described below.

[0149] First, a polishing solution and / or rinsing solution containing the polishing composition and / or semiconductor wetting agent according to the present invention are prepared. Preparing the polishing solution and / or rinsing solution involves adjusting the concentration, pH, and other operations on the polishing composition and / or semiconductor wetting agent to prepare the polishing solution and rinsing solution. For example, dilution can be used as a way to adjust the concentration. Alternatively, the polishing composition and / or semiconductor wetting agent may be used as the polishing solution and / or rinsing solution as is.

[0150] Next, the polishing solution and / or rinsing solution are supplied to the substrate, and polishing and / or rinsing are performed by conventional methods. For example, when performing final polishing and / or rinsing of a silicon wafer, typically, the silicon wafer that has undergone the lapping process is set in a general polishing apparatus, and the polishing solution and / or rinsing solution are supplied to the surface of the silicon wafer to be polished through the polishing pad of the apparatus. Typically, while continuously supplying the polishing solution and / or rinsing solution, the polishing pad is pressed against the surface of the silicon wafer to be polished, and the two are moved relative to each other, for example, by rotation. Through this polishing process, the polishing and / or rinsing of the substrate is completed.

[0151] A polishing composition and / or semiconductor wetting agent according to one embodiment of the present invention can be preferably applied to polishing and rinsing processes of substrates such as silicon wafers. The substrate may have undergone general treatments that can be applied to the substrate in processes upstream of the polishing and rinsing processes, such as lapping and etching, prior to the polishing and / or rinsing processes using the polishing composition and / or semiconductor wetting agent according to the present invention.

[0152] The polishing compositions and / or semiconductor wetting agents disclosed herein can be preferably used, for example, in polishing or rinsing substrates (e.g., silicon wafers) whose surface roughness has been prepared to a surface state of 0.01 nm to 100 nm by an upstream process. The surface roughness Ra of the above substrate can be measured, for example, using a laser scanning surface roughness meter "TMS-3000WRC" manufactured by SchmittMeasurement System Inc. The polishing compositions and / or semiconductor wetting agents disclosed herein are effective when used in final polishing, polishing immediately preceding it, or rinsing, and are particularly preferred for use in final polishing. Here, final polishing refers to the last polishing step in the manufacturing process of the target object, i.e., a step after which no further polishing is performed. The polishing compositions disclosed herein may also be used in polishing steps upstream of final polishing. Here, polishing steps upstream of final polishing refer to pre-polishing steps between the rough polishing step and the final polishing step. Typically, this process includes at least a primary polishing step, and may further include secondary, tertiary, etc. polishing steps. The semiconductor wetting agents disclosed herein may be used in a rinsing step performed after a polishing step upstream of the final polishing.

[0153] (Concentrate) The polishing compositions and / or semiconductor wetting agents disclosed herein may be in a concentrated form before being supplied to the substrate. That is, the polishing compositions and / or semiconductor wetting agents are in the form of concentrated polishing solutions and / or rinsing solutions, and can also be understood as stock solutions of polishing solutions and / or rinsing solutions. Polishing compositions and / or semiconductor wetting agents in such a concentrated form are advantageous in terms of convenience and cost reduction during manufacturing, distribution, storage, etc. The concentration ratio is not particularly limited and can be, for example, 2 to 100 times in terms of volume, and is usually appropriate at around 5 to 50 times (for example, 10 to 40 times).

[0154] (Diluted solution) The polishing compositions and / or semiconductor wetting agents disclosed herein are typically supplied to a substrate in the form of polishing and rinsing solutions containing the polishing compositions and / or semiconductor wetting agents and used for polishing and / or rinsing the substrate. The polishing and / or rinsing solutions may, for example, be prepared by diluting one of the polishing compositions and / or semiconductor wetting agents disclosed herein. The dilution is typically with water. Alternatively, the polishing compositions and / or semiconductor wetting agents may be used as polishing and / or rinsing solutions as they are. That is, the concept of polishing compositions and / or semiconductor wetting agents in the art disclosed herein encompasses both polishing (working slurry) and / or rinsing solutions supplied to a substrate and used for polishing and / or rinsing the substrate, and concentrated solutions, i.e., stock solutions of the polishing and / or rinsing solutions, that are diluted and used as polishing and / or rinsing solutions. Other examples of polishing solutions and / or rinsing solutions containing the polishing composition and / or semiconductor wetting agent disclosed herein include polishing solutions and / or rinsing solutions obtained by adjusting the pH of the composition.

[0155] The abrasive content in the above-mentioned concentrated liquid is not particularly limited, but can be, for example, 50% by mass or less. From the viewpoint of the handling of the above-mentioned concentrated liquid, such as the dispersion stability and filterability of the abrasive, the abrasive content in the above-mentioned concentrated liquid is usually preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less. Furthermore, from the viewpoint of convenience and cost reduction during manufacturing, distribution, storage, etc., the abrasive content can be, for example, 0.5% by mass or more, preferably 1% by mass or more, more preferably 2% by mass or more, for example 3% by mass or more. In one preferred embodiment, the abrasive content may be 4% by mass or more, or 5% by mass or more.

[0156] The abrasive content in the above-mentioned diluent is not particularly limited, but can be, for example, 25% by mass or less. From the viewpoint of the handling of the above-mentioned diluent (e.g., dispersion stability of abrasive particles) and surface quality after polishing, the abrasive content in the above-mentioned diluent is usually preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 1% by mass or less, and particularly preferably 0.5% by mass or less. Furthermore, from the viewpoint of convenience and cost reduction during manufacturing, distribution, storage, etc., the abrasive content can be, for example, 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 0.2% by mass or more, for example 0.5% by mass or more. In one preferred embodiment, the abrasive content may be 1% by mass or more, or 3% by mass or more.

[0157] Such a concentrated solution can be used in a manner in which it is diluted at a desired timing to prepare a polishing solution (working slurry) and / or a rinsing solution, and the polishing solution and / or rinsing solution is supplied to the substrate. The dilution can be performed, for example, by adding water to the concentrated solution and mixing it.

[0158] The polishing compositions and / or semiconductor wetting agents used in the technologies disclosed herein may be mono-component, or multi-component, including two-component types. For example, the polishing composition may be configured to prepare a polishing solution by mixing part A, which contains at least abrasive grains, with part B, which contains at least a portion of the remaining components, and mixing and diluting these at appropriate times as needed. Alternatively, the semiconductor wetting agent may be configured to prepare a rinsing solution by mixing part A, which contains some of the components, with part B, which contains at least a portion of the remaining components, and mixing and diluting these at appropriate times as needed.

[0159] (Polishing pad) The polishing pads used in the polishing and / or rinsing processes described above are not particularly limited. For example, polishing pads of the foamed polyurethane type, nonwoven fabric type, suede type, etc., can be used. Each polishing pad may or may not contain abrasive grains. Generally, polishing pads that do not contain abrasive grains are preferred.

[0160] (Washing) A substrate polished and / or rinsed with a polishing composition and / or semiconductor wetting agent according to one embodiment of the present invention is typically cleaned. Cleaning can be performed using a suitable cleaning solution. The cleaning solution used is not particularly limited, and for example, SC-1 cleaning solution, SC-2 cleaning solution, etc., which are common in fields such as semiconductors, can be used. An example of an SC-1 cleaning solution is a mixture of ammonium hydroxide (NH4OH), hydrogen peroxide (H2O2), and water (H2O). An example of an SC-2 cleaning solution is a mixture of HCl, H2O2, and H2O. The temperature of the cleaning solution can be, for example, in the range of room temperature or higher, up to about 90°C. Room temperature is typically about 15°C to 25°C. From the viewpoint of improving the cleaning effect, a cleaning solution of about 40°C to 85°C can be preferably used.

[0161] (Application) A polishing composition and / or semiconductor wetting agent according to one embodiment of the present invention can be particularly preferably used for polishing and / or rinsing a silicon surface, typically a silicon wafer. A typical example of a silicon wafer is a silicon single-crystal wafer (single-crystal silicon wafer), for example, a silicon single-crystal wafer obtained by slicing a silicon single-crystal ingot. A polishing composition and / or semiconductor wetting agent according to one embodiment of the present invention can be suitably used for polishing and / or rinsing a substrate having a silicon surface.

[0162] (substrate) A polishing composition and / or semiconductor wetting agent according to one embodiment of the present invention can be applied to polishing and / or rinsing substrates having various materials and shapes. The substrate material may be, for example, metals or metalloids such as silicon, aluminum, nickel, tungsten, copper, tantalum, titanium, stainless steel, or alloys thereof; glassy materials such as quartz glass, aluminosilicate glass, and glassy carbon; ceramic materials such as alumina, silica, sapphire, silicon nitride, tantalum nitride, and titanium carbide; compound semiconductor substrate materials such as silicon carbide, gallium nitride, and gallium arsenide; resin materials such as polyimide resin; and so on. The substrate may also be composed of multiple materials from among these. [Examples]

[0163] The present invention will be described in more detail using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. Unless otherwise specified, "%" and "parts" mean "mass%" and "parts by mass," respectively.

[0164] <Manufacturing of hydroxyethylcellulose> [Dissolution process] Each aqueous solution of hydroxyethylcellulose (HEC) was prepared by adding 2 parts by mass of each raw material hydroxyethylcellulose (HEC) to 98 parts by mass of deionized water (DIW) as a solvent, mixing and dissolving them to obtain the composition shown in Table 1 below.

[0165] (Raw material: hydroxyethylcellulose) HEC1: Weight average molecular weight (Mw): 3.65×10^5, powder, HEC2: Weight average molecular weight (Mw): 1.18×10^6, powder, Here, "10^X" (where X is any integer) is 10 X This represents [something]. The same applies below.

[0166] The weight-average molecular weights (Mw) of HEC1 and HEC2 are those obtained according to the evaluation method for the weight-average molecular weight (Mw) of hydroxyethylcellulose, which will be described later.

[0167] [Collision process] The raw material HEC aqueous solution obtained in the dissolution process was placed in a jet mill (manufactured by Sugino Machine Co., Ltd., product name: Starburst Lab). Subsequently, the jet mill was operated at the output (pressure) shown in Table 1 below, causing the raw material HEC aqueous solutions to collide with each other and apply pressure to the raw material HEC aqueous solution. The processing was performed once. The amount of raw material HEC aqueous solution processed was approximately 5000 mL, and the processing liquid flow rate and processing time are as shown in Table 1 below. The processing time was calculated by dividing the amount of raw material HEC aqueous solution processed by the processing liquid flow rate.

[0168] [Table 1]

[0169] The raw material HEC aqueous solution (treated HEC aqueous solution) that had undergone the collision process was recovered, and the following evaluations were then performed.

[0170] <Evaluation of hydroxyethylcellulose> ≪Weight-average molecular weight, number-average molecular weight, and molecular weight distribution≫ The weight-average molecular weight (Mw), number-average molecular weight (Mn), and molecular weight distribution of hydroxyethylcellulose in each of the above raw material HEC aqueous solutions and each treated HEC aqueous solution were measured by GPC using the following apparatus and conditions. The results using HEC1 as the raw material water-soluble polymer are shown in Table 2 below, and the results using HEC2 as the raw material water-soluble polymer are shown in Table 3 below.

[0171] [GPC measurement conditions] Measurement device: HLC-8420 GPC manufactured by Tosoh Corporation Column: TSKgel GMPWXL manufactured by Tosoh Corporation Molecular weight marker: Polyethylene oxide-polyethylene glycol, manufactured by Agilent Technologies. Eluent: 0.1M NaNO3 Flow rate: 1.0ml / min.

[0172] For each of the above raw material HEC aqueous solutions and each treated HEC aqueous solution, the GPC elution curves (RI (mV) - elution time (min) curves) obtained by the GPC method described above were examined. Figure 1 shows the GPC elution curve when HEC1 is used as the raw material water-soluble polymer, and Figure 2 shows the GPC elution curve when HEC2 is used as the raw material water-soluble polymer.

[0173] The differential molecular weight distribution curves were examined from each of these GPC elution curves. Figure 3 shows the differential molecular weight distribution curve when HEC1 was used as the raw material water-soluble polymer, and Figure 4 shows the differential molecular weight distribution curve when HEC2 was used as the raw material water-soluble polymer. The differential molecular weight distribution curves were created using a general method with the control and analysis software "Eco SEC-WS" used in the above GPC measurement device.

[0174] ≪Selective removal of high molecular weight compounds in treated HEC≫ In aqueous solutions containing each of the HECs to be treated, the selective removal of high molecular weight compounds was confirmed by measuring (1) the amount of high molecular weight compounds before and after the collision process, (2) the amount of low molecular weight compounds before and after the collision process, and (3) the change in peak top molecular weight (Mp). The results are shown in Tables 2 and 3 below.

[0175] ≪Changes in molecular weight distribution before and after the collision process≫ Tables 2 and 3 below show the molecular weight distribution (Mw / Mn) values ​​obtained by the GPC method for hydroxyethylcellulose in each of the above raw material HEC aqueous solutions and each HEC aqueous solution being treated. Tables 2 and 3 also show the ratio (%) of the Mw / Mn of hydroxyethylcellulose in each HEC aqueous solution being treated to the Mw / Mn of hydroxyethylcellulose in each raw material HEC aqueous solution.

[0176] ≪Amount of metal impurities≫ The amount of metal element impurities was confirmed by measuring the metal impurity concentration of the raw material HEC aqueous solution and the treated HEC aqueous solution, using HEC1 as the raw material water-soluble polymer, by inductively coupled plasma (ICP) emission spectrometry. The apparatus used was the "ICP-AES (model number: ICPS-8100)" manufactured by Shimadzu Corporation.

[0177] ≪Filtration properties≫ 100g of each raw material HEC aqueous solution and each HEC aqueous solution to be treated were measured out and diluted with deionized water (DIW) to prepare 1% by mass aqueous solutions. The prepared aqueous solutions were filtered by suction using a filtration filter (filter material: polyethersulfone membrane, pore size: 0.2 μm). The flow time (min) was measured. Similarly, 100g of deionized water (DIW) was also filtered by suction and the flow time (sec) was measured. Here, the flow time is defined as the time from the start of filtration until all the liquid has passed through the filtration filter. For suction filtration, an aspirator (product name), model MDA-015 (manufactured by ULVAC, Inc.) was used, and the maximum vacuum pressure during the filtration test was approximately 0.5 kPa. The filtration index was evaluated by the ratio of the flow time of the raw material HEC aqueous solution or the HEC aqueous solution to the flow time of the DIW (flow time of raw material HEC aqueous solution or the HEC aqueous solution to be treated (min) / flow time of DIW (sec)). A smaller value for the filtration index indicates better filterability. The results using HEC1 as the raw material are shown in Table 2 below, and the results using HEC2 as the raw material are shown in Table 3 below.

[0178] [Table 2]

[0179] [Table 3]

[0180] From the results in Table 2 above, it was confirmed that the hydroxyethyl cellulose obtained in Examples 1 to 3 through the aforementioned dissolution and collision steps, compared to the hydroxyethyl cellulose obtained in Comparative Example 1, which did not undergo the aforementioned collision step, showed good maintenance of the amount of low molecular weight particles while selectively removing high molecular weight particles, and the filterability of the solution was also significantly superior.

[0181] From the results in Table 3 above, it was confirmed that the hydroxyethyl cellulose obtained in Examples 4 to 6 through the aforementioned dissolution and collision steps, compared to the hydroxyethyl cellulose obtained in Comparative Example 2 which did not undergo the aforementioned collision step, showed good maintenance of the amount of low molecular weight particles while selectively removing high molecular weight particles, and the filterability of the solution was also significantly superior.

[0182] More specifically, it was confirmed that the Mw / Mn ratio decreased from 17% to 87% in the hydroxyethylcellulose of these examples. This indicates that the molecular weight distribution of hydroxyethylcellulose narrowed, resulting in hydroxyethylcellulose with a uniform weight molecular weight. Furthermore, it was confirmed that the amount of high molecular weight material decreased from 36% to 93%. The change in the amount of low molecular weight material was confirmed to be within ±1%. In addition, the change in peak top molecular weight (Mp) was confirmed to be within ±5%.

[0183] Furthermore, the measurement results of the amount of metal impurities confirmed that the amount of metal impurities in the treated water-soluble polymer did not increase. This result is thought to be because the process of colliding solutions and applying pressure to the solution, as performed in the example, was able to avoid the inclusion of metal impurities.

[0184] <Preparation of polishing composition> (Examples 1-4, Comparative Examples 1 and 2) A concentrated solution of polishing composition was prepared by mixing the above-mentioned treated HEC aqueous solution, abrasive grains, a basic compound, an arbitrary polymer, a surfactant, and deionized water (DIW). Colloidal silica with an average primary particle diameter of 27 nm was used as the abrasive grains, 29% aqueous ammonia was used as the basic compound, untreated polyvinyl alcohol with a weight-average molecular weight of 70,000 was used as the arbitrary polymer, and a block copolymer of EO and PO (PEO-PPO-PEO type triblock copolymer) was used as the surfactant. Each polishing composition was obtained by diluting the concentrated solution of polishing composition with deionized water (DIW) at a volume ratio of 20. The concentrations of each component in the concentrated solution of polishing composition were 0.17 parts by mass of HEC, 3.5 parts by mass of abrasive grains, 0.1 parts by mass of basic compound, 0.001 parts by mass of arbitrary polymer, and 0.025 parts by mass of surfactant. The concentration of abrasive particles in the diluent of the polishing composition is 0.175% by mass, and the concentration of HEC is 0.0085% by mass.

[0185] <Evaluation of abrasive compositions> ≪D90 Measurement≫ The D90 was measured for particles present in the polishing composition related to this example. A UPA-UT151 manufactured by Nikkiso Co., Ltd. was used for the measurement. The results using HEC1 as the raw material water-soluble polymer are shown in Table 4 below, and the results using HEC2 as the raw material water-soluble polymer are shown in Table 5 below.

[0186] Polishing Test 12-inch diameter single-crystal silicon wafer (conduction type: P-type, crystal orientation: <100> A resistivity of 0.1 Ω·cm or more and less than 100 Ω·cm was prepared, and after preliminary polishing according to the following preliminary polishing conditions, the main polishing was performed.

[0187] [Pre-polishing] The polishing solution used for preliminary polishing was obtained by diluting a concentrated solution of a composition prepared by mixing abrasive grains, a basic compound, and deionized water (DIW) with deionized water (DIW) to a volume ratio of 20. Colloidal silica with an average primary particle diameter of 42 nm was used as the abrasive grain, and potassium hydroxide was used as the basic compound. The concentration of abrasive grains in the diluted polishing solution was 1.0% by mass, and the concentration of the basic compound was 0.068% by mass.

[0188] [Pre-polishing conditions] Polishing equipment: Single-wafer polishing machine manufactured by Okamoto Machine Tool Works, Ltd., model "PNX-332B" Grinding load: 20kPa Plate rotation speed: 20 rpm Head rotation speed: 20 rpm Polishing pad: Manufactured by Fujibo Ehime Co., Ltd., product name "FP55" Polishing time: 100 seconds Polishing solution temperature: 20℃ Polishing fluid supply rate: 2.0 liters / minute (flow-through application).

[0189] [Main polishing] The polishing compositions prepared in each of the above examples were used as polishing solutions, and the silicon wafers obtained after the above preliminary polishing were polished under the following polishing conditions.

[0190] [Main polishing conditions] Polishing equipment: Single-wafer polishing machine manufactured by Okamoto Machine Tool Works, Ltd., model "PNX-332B" Grinding load: 15kPa Plate rotation speed: 30 rpm Head rotation speed: 30 rpm Polishing pad: Manufactured by Fujibo Ehime Co., Ltd., product name "POLYPAS27NX" Polishing time: 4 minutes Polishing solution temperature: 20℃ Polishing fluid supply rate: 2.0 liters / minute (flow-through application).

[0191] ≪LPD-N count measurement≫ The number of LPD-N particles present on the surface (polished surface) of the silicon wafer obtained by the above polishing process was measured using a wafer inspection device manufactured by KLA-Tencor, product name "SURFSCAN SP2," in the DCO mode of the device.

[0192] ≪Measurement of LPD count≫ The number of LPDs present on the surface (polished surface) of the silicon wafer obtained by the above polishing process was measured using a wafer inspection system manufactured by KLA-Tencor, product name "SURFSCAN SP2," in the DCO mode of the system.

[0193] The evaluation results for LPD-N and LPD are shown in Tables 4 and 5 below, respectively. Note that the LPD-N and LPD values ​​in Tables 4 and 5 are relative values, with the LPD-N and LPD values ​​of Comparative Examples 1 and 2 set to 100%.

[0194] [Table 4]

[0195] [Table 5]

[0196] From the results in Tables 4 and 5 above, it was confirmed that the D90 value of the polishing composition according to the examples decreased. This is thought to be because the amount of high molecular weight polymers in the raw material water-soluble polymer contained in the polishing composition decreased, and / or the diameter of the molecular chains of the high molecular weight polymers decreased. Generally, the larger the weight molecular weight of a polymer, the easier it is to adsorb to abrasive particles, and further abrasive particles are adsorbed onto the adsorbed water-soluble polymer, resulting in coarse particles. In the polishing composition according to the examples, it is thought that the D90 of the polishing composition containing water-soluble polymers decreased because the high molecular weight polymers in the raw material water-soluble polymers, which can be the cause of producing such coarse particles, were removed.

[0197] Furthermore, the results from Tables 4 and 5 above confirm that when using a polishing composition containing a water-soluble polymer obtained through the impact process, the amounts of LPD-N and LPD are significantly lower compared to a polishing composition containing a water-soluble polymer that has not undergone the impact process.

[0198] Furthermore, as mentioned above, it has been confirmed that the hydroxyethyl cellulose in the examples suppresses the increase in metal impurities. Therefore, it is believed that in polishing compositions prepared using such hydroxyethyl cellulose or aqueous solutions containing it, it is possible to prevent an increase in the number and size of coarse particles and the amount of metal impurities, and that the amount of surface defects resulting from this is also reduced.

Claims

1. A polishing composition comprising abrasive particles and a water-soluble polymer, The water-soluble polymer is The process involves dissolving the raw material water-soluble polymer in a solvent to create a solution, A step of causing the solutions to collide with each other and applying pressure to the solutions, A water-soluble polymer treated by a method including, The aforementioned water-soluble polymer raw material is a cellulose derivative, The following conditions [1] must be met: At least one selected from the group consisting of [2] and [3] below is further satisfied: Polishing composition; [1] When the value of the vertical axis dw / d(LogM) in the differential molecular weight distribution curve of the water-soluble polymer is 20, the larger of the two values ​​of LogM on the horizontal axis is defined as LogM(R), and when the value of the vertical axis dw / d(LogM) in the differential molecular weight distribution curve of the water-soluble polymer is 20, the larger of the two values ​​of LogM on the horizontal axis is defined as LogM(P), then the ratio of LogM(P) to LogM(R) is less than 98%; [2] When the value of LogM on the horizontal axis in the differential molecular weight distribution curve of the water-soluble polymer is 4.5, the value of dw / d(LogM) on the vertical axis is defined as dw / d(LogM(r)), and when the value of LogM on the horizontal axis in the differential molecular weight distribution curve of the water-soluble polymer is 4.5, the value of dw / d(LogM(p)) on the vertical axis is defined as dw / d(LogM(p)), and the ratio of dw / d(LogM(p)) to dw / d(LogM(r)) is within the range of 98% or more and 105% or less; [3] When the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer raw material is defined as LogM(r_peak), and the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer is defined as LogM(p_peak), the ratio of LogM(p_peak) to LogM(r_peak) is within the range of 100±5%.

2. The polishing composition according to claim 1, wherein the step of applying pressure to the solution is a step of performing a jet mill treatment.

3. The polishing composition according to claim 2, wherein in the step of performing the jet milling treatment, the treatment pressure is 5 MPa or more and 900 MPa or less, the treatment time is 1 minute or more and 600 minutes or less, the treatment liquid flow rate is 10 mL / min or more and 100,000 mL / min or less, and the number of treatments is 1 or more and 20 or less.

4. An abrasive composition according to any one of claims 1 to 3, satisfying all of the above conditions [1], [2], and [3].

5. The polishing composition according to any one of claims 1 to 4, wherein the weight-average molecular weight (Mw) / number-average molecular weight (Mn) of the water-soluble polymer is 30 or less.

6. The polishing composition according to claim 5, wherein the weight-average molecular weight (Mw) / number-average molecular weight (Mn) of the water-soluble polymer is 10 or less.

7. The polishing composition according to any one of claims 1 to 6, wherein the weight-average molecular weight of the cellulose derivative is 2,000 or more and 4,000,000 or less.

8. A method for producing an abrasive composition comprising abrasive particles and a water-soluble polymer, The dissolution process involves dissolving the raw material water-soluble polymer in a solvent to create a solution, A collision step in which the solutions collide with each other and pressure is applied to the solutions, The process includes obtaining the water-soluble polymer by a method comprising the following: The process further includes a step of mixing abrasive particles into the solution obtained through the aforementioned collision step, The aforementioned water-soluble polymer raw material is a cellulose derivative, The step of applying pressure to the aforementioned solution is a jet milling process, In the jet milling process described above, the processing pressure is 5 MPa or more and 900 MPa or less, the processing time is 1 minute or more and 600 minutes or less, the processing liquid flow rate is 10 mL / min or more and 100,000 mL / min or less, and the number of processing cycles is 1 or more and 20 or less. A method for producing an abrasive composition.

9. A method for producing the polishing composition according to claim 8, satisfying at least one selected from the group consisting of [1], [2], [3], and [4] below; [1] When the value of the vertical axis dw / d(LogM) in the differential molecular weight distribution curve of the water-soluble polymer is 20, the larger of the two values ​​of LogM on the horizontal axis is defined as LogM(R), and when the value of the vertical axis dw / d(LogM) in the differential molecular weight distribution curve of the water-soluble polymer is 20, the larger of the two values ​​of LogM on the horizontal axis is defined as LogM(P), then the ratio of LogM(P) to LogM(R) is less than 98%; [2] When the value of LogM on the horizontal axis in the differential molecular weight distribution curve of the water-soluble polymer is 4.5, the value of dw / d(LogM) on the vertical axis is defined as dw / d(LogM(r)), and when the value of LogM on the horizontal axis in the differential molecular weight distribution curve of the water-soluble polymer is 4.5, the value of dw / d(LogM(p)) on the vertical axis is defined as dw / d(LogM(p)), and the ratio of dw / d(LogM(p)) to dw / d(LogM(r)) is within the range of 98% or more and 105% or less; [3] When the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer raw material is defined as LogM(r_peak), and the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer is defined as LogM(p_peak), the ratio of LogM(p_peak) to LogM(r_peak) is within the range of 100±5%; [4] The weight-average molecular weight (Mw) / number-average molecular weight (Mn) of the water-soluble polymer is 30 or less.

10. A method for producing an abrasive composition according to claim 8 or 9, further comprising the step of filtering the solution after the step of applying pressure to the solution and before the step of mixing abrasive particles into the solution.

11. A method for producing an abrasive composition according to any one of claims 8 to 10, further comprising the step of filtering the solution after the step of mixing abrasive particles into the solution.

12. A method for producing the polishing composition according to any one of claims 8 to 11, wherein the weight-average molecular weight of the cellulose derivative is 2,000 or more and 4,000,000 or less.

13. A semiconductor wetting agent containing a water-soluble polymer, The water-soluble polymer is The process involves dissolving the raw material water-soluble polymer in a solvent to create a solution, A step of causing the solutions to collide with each other and applying pressure to the solutions, A water-soluble polymer treated by a method including, The aforementioned water-soluble polymer raw material is a cellulose derivative, The following conditions [1] must be met: At least one selected from the group consisting of [2] and [3] below is further satisfied: Wetting agents for semiconductors; [1] When the value of the vertical axis dw / d(LogM) in the differential molecular weight distribution curve of the water-soluble polymer is 20, the larger of the two values ​​of LogM on the horizontal axis is defined as LogM(R), and when the value of the vertical axis dw / d(LogM) in the differential molecular weight distribution curve of the water-soluble polymer is 20, the larger of the two values ​​of LogM on the horizontal axis is defined as LogM(P), then the ratio of LogM(P) to LogM(R) is less than 98%; [2] When the value of LogM on the horizontal axis in the differential molecular weight distribution curve of the water-soluble polymer is 4.5, the value of dw / d(LogM) on the vertical axis is defined as dw / d(LogM(r)), and when the value of LogM on the horizontal axis in the differential molecular weight distribution curve of the water-soluble polymer is 4.5, the value of dw / d(LogM(p)) on the vertical axis is defined as dw / d(LogM(p)), and the ratio of dw / d(LogM(p)) to dw / d(LogM(r)) is within the range of 98% or more and 105% or less; [3] When the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer raw material is defined as LogM(r_peak), and the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer is defined as LogM(p_peak), the ratio of LogM(p_peak) to LogM(r_peak) is within the range of 100±5%.

14. The semiconductor wetting agent according to claim 13, wherein the step of applying pressure to the solution is a step of performing a jet mill treatment.

15. The semiconductor wetting agent according to claim 14, wherein in the step of performing the jet milling process, the processing pressure is 5 MPa or more and 900 MPa or less, the processing time is 1 minute or more and 600 minutes or less, the processing liquid flow rate is 10 mL / min or more and 100,000 mL / min or less, and the number of processing cycles is 1 or more and 20 or less.

16. A semiconductor wetting agent according to any one of claims 13 to 15, satisfying all of the above conditions [1], [2], and [3].

17. The semiconductor wetting agent according to any one of claims 13 to 16, wherein the weight-average molecular weight (Mw) / number-average molecular weight (Mn) of the water-soluble polymer is 30 or less.

18. The semiconductor wetting agent according to claim 17, wherein the weight-average molecular weight (Mw) / number-average molecular weight (Mn) of the water-soluble polymer is 10 or less.

19. The semiconductor wetting agent according to any one of claims 13 to 18, wherein the weight-average molecular weight of the cellulose derivative is 2,000 or more and 4,000,000 or less.

20. A method for producing a semiconductor wetting agent containing a water-soluble polymer, The dissolution process involves dissolving the raw material water-soluble polymer in a solvent to create a solution, A collision step in which the solutions collide with each other and pressure is applied to the solutions, The process includes obtaining the water-soluble polymer by a method comprising the following: The aforementioned water-soluble polymer raw material is a cellulose derivative, The step of applying pressure to the aforementioned solution is a jet milling process, In the jet milling process described above, the processing pressure is 5 MPa or more and 900 MPa or less, the processing time is 1 minute or more and 600 minutes or less, the processing liquid flow rate is 10 mL / min or more and 100,000 mL / min or less, and the number of processing cycles is 1 or more and 20 or less. A method for manufacturing semiconductor wetting agents.

21. The method for producing a semiconductor wetter according to claim 20, further comprising the step of mixing other components into the solution obtained through the collision step.

22. A method for producing a semiconductor wetting agent according to claim 20 or 21, satisfying at least one selected from the group consisting of [1], [2], [3], and [4] below; [1] When the value of the vertical axis dw / d(LogM) in the differential molecular weight distribution curve of the water-soluble polymer is 20, the larger of the two values ​​of LogM on the horizontal axis is defined as LogM(R), and when the value of the vertical axis dw / d(LogM) in the differential molecular weight distribution curve of the water-soluble polymer is 20, the larger of the two values ​​of LogM on the horizontal axis is defined as LogM(P), then the ratio of LogM(P) to LogM(R) is less than 98%; [2] When the value of LogM on the horizontal axis in the differential molecular weight distribution curve of the water-soluble polymer is 4.5, the value of dw / d(LogM) on the vertical axis is defined as dw / d(LogM(r)), and when the value of LogM on the horizontal axis in the differential molecular weight distribution curve of the water-soluble polymer is 4.5, the value of dw / d(LogM(p)) on the vertical axis is defined as dw / d(LogM(p)), and the ratio of dw / d(LogM(p)) to dw / d(LogM(r)) is within the range of 98% or more and 105% or less; [3] When the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer raw material is defined as LogM(r_peak), and the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer is defined as LogM(p_peak), the ratio of LogM(p_peak) to LogM(r_peak) is within the range of 100±5%; [4] The weight-average molecular weight (Mw) / number-average molecular weight (Mn) of the water-soluble polymer is 30 or less.

23. A method for producing a semiconductor wetter according to any one of claims 20 to 22, wherein the weight-average molecular weight of the cellulose derivative is 2,000 or more and 4,000,000 or less.

24. The process involves dissolving the raw material water-soluble polymer in a solvent to create a solution, A step of causing the solutions to collide with each other and applying pressure to the solutions, A water-soluble polymer treated by a method including, Here, the raw material water-soluble polymer is a cellulose derivative, The aforementioned water-soluble polymer is used in polishing compositions and / or as a wetting agent for semiconductors. The water-soluble polymer is The following conditions [1] must be met: At least one selected from the group consisting of [2] and [3] below is further satisfied; [1] When the value of the vertical axis dw / d(LogM) in the differential molecular weight distribution curve of the water-soluble polymer is 20, the larger of the two values ​​of LogM on the horizontal axis is defined as LogM(R), and when the value of the vertical axis dw / d(LogM) in the differential molecular weight distribution curve of the water-soluble polymer is 20, the larger of the two values ​​of LogM on the horizontal axis is defined as LogM(P), then the ratio of LogM(P) to LogM(R) is less than 98%; [2] When the value of LogM on the horizontal axis in the differential molecular weight distribution curve of the water-soluble polymer is 4.5, the value of dw / d(LogM) on the vertical axis is defined as dw / d(LogM(r)), and when the value of LogM on the horizontal axis in the differential molecular weight distribution curve of the water-soluble polymer is 4.5, the value of dw / d(LogM(p)) on the vertical axis is defined as dw / d(LogM(p)), and the ratio of dw / d(LogM(p)) to dw / d(LogM(r)) is within the range of 98% or more and 105% or less; [3] When the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer raw material is defined as LogM(r_peak), and the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer is defined as LogM(p_peak), the ratio of LogM(p_peak) to LogM(r_peak) is within the range of 100±5%.

25. The water-soluble polymer according to claim 24, wherein the step of applying pressure to the solution is a step of performing a jet mill treatment.

26. The water-soluble polymer according to claim 25, wherein in the step of performing the jet milling process, the processing pressure is 5 MPa or more and 900 MPa or less, the processing time is 1 minute or more and 600 minutes or less, the processing liquid flow rate is 10 mL / min or more and 100,000 mL / min or less, and the number of processing cycles is 1 or more and 20 or less.

27. A water-soluble polymer according to any one of claims 24 to 26, satisfying all of the above [1], [2], and [3].

28. The water-soluble polymer according to any one of claims 24 to 27, wherein the weight-average molecular weight (Mw) / number-average molecular weight (Mn) of the water-soluble polymer is 30 or less.

29. The water-soluble polymer according to claim 28, wherein the weight-average molecular weight (Mw) / number-average molecular weight (Mn) of the water-soluble polymer is 10 or less.

30. The water-soluble polymer according to any one of claims 24 to 29, wherein the weight-average molecular weight of the cellulose derivative is 2,000 or more and 4,000,000 or less.

31. A method for polishing a substrate using the polishing composition described in any one of claims 1 to 7.

32. The method according to claim 31, wherein the substrate is a single-crystal silicon wafer.

33. A method for rinsing a substrate using a semiconductor wetting agent according to any one of claims 13 to 19.

34. The method according to claim 33, wherein the substrate is a single-crystal silicon wafer.

Citation Information

Patent Citations

  • Abrasive and production method therefor

    JP2004244566A

  • Polishing composition, polishing composition manufacturing method and semiconductor substrate manufacturing method using polishing composition

    JP2014036206A

  • Polishing composition and manufacturing method for substrate

    JP2014049633A

  • Method for producing hydrophobized hydroxyethyl cellulose and polishing aid

    JP2019104781A

  • Polishing fluid for metallic film and method for producing semiconductor substrate using the same

    WO2003021651A1